Microbial oil production by Yarrowia lipolytica strains using glycerol as carbon source - Elisa Duarte Guerra Coelho; Fernanda Palladino; Elisa A. A. Teixeira; Fernanda L. C. Oliveira; Vânya M. D. Pasa; Luiz H. Rosa; Carlos A. Rosa (Brazilian Journal of Microbiology, 2026)
Yeasts can produce microbial oil from hydrophobic substrates such as glycerol, a byproduct of the biodiesel industry that is often undervalued in the market. Yarrowia lipolytica is capable of degrading glycerol and is considered a model organism for studying lipid accumulation. Different yeast strains and culture conditions can result in varying lipid yields with distinct fatty acid profiles. Thus, in this study, five strains of Y. lipolytica were tested for microbial oil production using pure glycerol at temperatures of 15 °C and 25 °C. None of the isolates were considered oleaginous at 15 °C. However, at 25 °C, the isolates UFMG-CM-Y6114 (from cheese), UFMG-CM-Y4187 (from beach sand), and UFMG-CM-Y6189 (from Antarctica) produced more than 20% lipid content (29.30%, 26.95%, and 34.38%, respectively). No significant differences in lipid content were observed between the UFMG-CM-Y6114 and UFMG-CM-Y4187 strains. The cheese- and Antarctica-derived strains were further tested for their ability to accumulate oil when grown on crude glycerol. Among them, UFMG-CM-Y6189 showed the best performance, producing 9.40 g·L⁻¹ of biomass, 1.90 g·L⁻¹ of lipid yield, and 21.56% lipid content, while consuming 61.3 g·L⁻¹ of glycerol. The fatty acid profile of these lipids was predominantly monounsaturated (59.5%), with oleic acid (49.4%) as the main component. This, combined with a low polyunsaturated fatty acid content (5.2%), makes these lipids particularly suitable for biodiesel production. Therefore, the lipids from the Y. lipolytica strain UFMG-CM-Y6189 represent a promising raw material for biodiesel production from glycerol.

Low hatching success at major green turtle rookeries in northern Saudi Arabian Red Sea - Lyndsey K. Tanabe; Kirsty Scott; Mohammed F. Khayat; Royale S. Hardenstine; Jesse E.M. Cochran; Hector Barrios-Garrido; Takahiro Shimada; Carlos M. Duarte; Michael L. Berumen (Journal of Experimental Marine Biology and Ecology, 2026)

Associations between teat apex, milk microbiota, and udder health in primiparous cows: Effects of decontamination in a low biomass context - José A. Ferronatto; Eduardo M. Ramos-Sanchez; Erika K. Ganda; Marcos B. Heinemann; Juliano L. Gonçalves; Marcos V. dos Santos; Julia A. Arantes; Vinicius S. Duarte; Alessandro S. Guimarães; Marcio C. Costa; Marie Joossens; Sarne De Vliegher; et al. (Research in Veterinary Science, 2026)

Commentary on "Solvent-mediated construction of phosphate/carboxyl bifunctional hyper-cross-linked polymers for highly efficient uranium removal from aqueous solutions (https://doi.org/10.1016/j.jhazmat.2026.141094)" - Ellen S.A. Duarte; Larissa L. Fernandes; Eder C. Lima (Journal of Hazardous Materials, 2026)

The uppermost Sinemurian and Sinemurian–Pliensbachian transition in Western and Northern Iberia: A chronostratigraphic review and correlation framework - Íñigo Vitón; María José Comas-Rengifo; Luís V. Duarte; Ricardo L. Silva; Antonio Goy (Earth-Science Reviews, 2026)

Evaluation of rapid evaporative ionization mass spectrometry (REIMS) relationships with biochemical markers of tenderness in beef Longissimus lumborum steaks - Kaitlyn R. Loomas; Dale R. Woerner; Ben M. Bohrer; Tyson R. Brown; Heather L. Bruce; Marcio S. Duarte; Bimol C. Roy; Yifei Wang; Katie Pedgerachny; Jerrad F. Legako (Meat Science, 2026)

Maternal chromium propionate supplementation in late gestation and its association with cow performance and skeletal muscle programming in beef calves - Emily A. Knapper; Luiza V. Kladt; Ivan I. Avalos-Rosario; Sarah E. Dean; Walmir Silva; Nicola V.L. Serão; Jerilyn E. Hergenreder; Elliot L. Neto; Katharine M. Wood; Michael A. Steele; Matheus P. Gionbelli; Marcio S. Duarte (Animal Feed Science and Technology, 2026)

Unraveling the ecological impact of textile microfibers: Current knowledge and research challenges - Khawla Chouchene; Ana L. Patrício Silva; Ana Costa; Andréa Marinho; Armando C. Duarte; Teresa Rocha-Santos; João P. da Costa (Marine Pollution Bulletin, 2026)

Veterinary perspectives on biosecurity measures in small-scale farming systems across European countries: Results from a cross-national survey - F. Duarte; J. Prodanov-Radulović; B. Mehmedi; A. Piccirillo; M. Stukelj; E. Kldiashvili; V. Nedosekov; B. Milovanovic; N.D. Ayaz; R. Yildiz; S. Meling; I. Toftaker; et al. (Research in Veterinary Science, 2026)

Microbial Responses to Warming Reduce Deep Blue Carbon Storage - Leilei Xiao; Jian Liu; Genevieve L. Noyce; Jaehyun Lee; Carlos M. Duarte; Meng Zhou; Min Luo; Ruifeng Sun; Run Dang; Lifeng Zhou; Lirong Zhang; Chuancheng Fu; et al. (Global Change Biology, 2026)
Coastal wetlands are critical blue carbon reservoirs, yet the depth‐resolved impacts of warming on belowground carbon dynamics remain poorly understood. Over the course of an 8‐year in situ experiment, we investigated plant‐derived carbon inputs, soil carbon losses via respiration, and microbially mediated carbon fixation across a 60 cm soil profile under a projected 2°C atmospheric warming scenario. Plant carbon fixation (above‐ and belowground net primary productivity) and soil respiration exhibited synchronized responses to warming, with an initial increase, followed by a decline in the mid‐term, and no significant response in the later stages. Soil and microbial respiration stabilized after prolonged exposure to elevated temperatures, as these processes were constrained by substrate availability. In contrast, phospholipid fatty acid profiling, amino sugar biomarkers, and metagenome‐assembled genomes consistently indicated a greater than one‐third reduction in microbial carbon fixation within subsoils (40–60 cm). Our fully factorial, depth‐stratified warming design reveals the particular vulnerability of deep soil microbial carbon retention to long‐term climate warming, independent of shifts in plant input or respiratory carbon loss. This work highlights underappreciated pathways influencing soil blue carbon dynamics in a changing world.

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Synthetic cannabinoids in hair: a review of recent findings and analytical methods by LC-MS/MS - Rafaela S. Pereira; Olívia B.O. Moreira; Marcone Augusto L. de Oliveira; Claudiane C. Canuto; Diogo O.C. Lemos; Lucas M. Duarte; Silvana V. Rodrigues (Analytica Chimica Acta, 2026)

Amazonian drought of 2023: Environmental conditions relevant to fishes - Ora E. Johannsson; Thiago L. Nascimento; Helen Agasild; Priit Zingel; Rafael M. Duarte; Gudrun de Boeck; Anne Cremazy; Jhonatan Mota da Silva; Carolyn Morris; Chris M. Wood; Adalberto L. Val (Journal of Fish Biology, 2026)
This paper provides a platform for the following studies within this Special Issue. ‘Ecophysiology of fishes in the two great tributaries of the Amazon in the Anthropocene’. It documents the water quality conditions and accompanying zooplankton community structure and biomass relative to fish health in the Rio Negro and Rio Solimões during the extreme drought of 2023. Our goals were to document conditions, compare them with historical data and assess their implications for the resident fishes. During the 2023 drought, fishes in the Rio Negro came under more pressure from environmental changes than fishes in the Rio Solimões. Habitats became smaller and less diverse than normally observed by the end of the annual drought in both rivers. In some areas, fishes experienced elevated temperatures and/or reduced oxygen especially in the floodplain lakes and shallower areas. In the Rio Negro, increases in total suspended solids (TSS) decreased the range of vision for resident fishes, which would have both protected them from predators and shielded their prey. The coincidence of higher temperatures and higher oxygen in the afternoon in the Rio Negro suggests that primary production still occurred in the shallower, lit surface waters. This would explain the presence of zooplankton near the water's surface. Predation was likely intense as the macro‐zooplankton were small, although, the effect of high temperatures on metabolic rates could also influence size. Cladoceran biomass showed a negative relationship with the mass of the 1.2−50 μm fraction of TSS. Higher TSS concentrations likely meant resuspension of sediments. Spectroscopic analysis showed that dissolved organic carbon (DOC) was more degraded than normal, and thus would have provided less protection against the effects of low pH on ionoregulation. Low pH and low conductivity put extreme stress on maintaining ion balance in the black waters. In the Rio Solimões, fish suffered less environmental change. Water temperature and oxygen concentrations were more moderate, although evidence suggests that temperature and conductivity have increased compared to historic data. The concentration of TSS was normal. The greatest change was a 200% to 300% increase in DOC, albeit the DOC was very degraded. This may have spurred the high biomass of bacteria which was out of balance with the other components of the microbial loop. The passage of energy from bacteria to higher zooplankton trophic levels worked efficiently in the Rio Negro but not the Rio Solimões. This study allows a better understanding of the stresses on the fish community in these adverse conditions and the implications for their future.

Contrasting thermal and hypoxic responses of species from blackwater and whitewater rivers - Susana Braz‐Mota; Rafael M. Duarte; Adalberto L. Val (Journal of Fish Biology, 2026)
In the Amazon basin, climate change is increasing water temperatures and CO₂ concentrations, which intensify environmental stressors for fish by increasing natural thermal regimes, reducing dissolved oxygen and pH levels. Extreme droughts, such as those recorded in 2023 and the new record set in 2024, have exacerbated these conditions and have led to widespread fish mortality. Amazonian rivers, which are characterized by contrasting whitewater and blackwater systems, provide unique habitats with distinct pHs and temperatures that shape biodiversity and species adaptations. With regional water temperatures projected to increase by 2.2–7.0°C by the end of the century, understanding the expected thermal vulnerability of Amazonian fish has become crucial. This study aims to investigate the influence of water type (blackwater vs. whitewater) on both thermal and hypoxia tolerances and hypoxia responses in different fish species following the extreme drought in 2023 and analyse these responses on individual and taxonomic levels. The results revealed significant variability in both thermal and hypoxia tolerances among species, with fish displaying a lower thermal safety margin in blackwaters. The contrasting thermal and hypoxia tolerances observed between blackwater and whitewater fishes highlight the complexity of their adaptive strategies in response to environmental stressors and are fundamental for predicting future conditions of the Amazonian environment under the current climate change scenario.

Joint effects of elevated copper and temperature in juvenile Tambaqui exposed in black and white waters of the Amazon - Anne Crémazy; Carolyn Morris; Susana Braz‐Mota; Chris M. Wood; Rafael M. Duarte; Ora E. Johannsson; Adalberto L. Val (Journal of Fish Biology, 2026)
This study aimed to investigate how exposure to elevated water temperature and metal concentration jointly affect the physiology of Amazonian fish. Aboard a research vessel in the Amazon, we evaluated the effects of water temperature (river T°C at 31.5°C and a + 4°C increase to 35.5°C) and of 3‐h copper (Cu) exposure (up to 600 μg/L) in juvenile Tambaqui ( Colossoma macropomum ) exposed in freshly collected Rio Negro (‘black water’) and Rio Solimões (‘white water’) waters. In Cu‐free water, the +4°C raise accelerated physiological Na + influx and efflux rates, but only in Rio Negro water. Temperature had no effects on the other physiological fluxes (Cl − , K + and ammonia fluxes). Cu exposure led to net losses of Na + (via increased efflux), Cl − and K + and decrease in acute upper thermal tolerance (CT max ). These Cu effects were more prominent in Rio Negro water, where Cu bioavailability was the greatest. The +4°C change had no effect on gill Cu accumulation and, overall, there was limited evidence that warming worsened Cu‐induced ionoregulatory disturbances. However, in Rio Negro, as Cu and heat both separately promoted Na + net losses, fish Na + balance was the most compromised in the presence of the two stressors. Altogether, the impaired thermotolerance and ionoregulation under combined Cu and heat exposures suggest a cumulative physiological interaction between two stressors that are increasing threats to the Amazon basin.

Paracoccus carotinifaciens as a bacterial source of astaxanthin for food applications: integrated experimental and in silico analysis reveals a safe non-antibacterial profile and weak selective fungistatic activity - Cassamo U. Mussagy; Jonatas L. Duarte; Felipe M. Tashiro; Camila C.B. Medeiros; Rodrigo Sorrechia; Rosemeire C.L.R. Pietro; Marlus Chorilli; Juan M. Guzmán-Flores; Angie V. Caicedo-Paz (Food Bioscience, 2026)

Unravelling the molecular mechanisms of vegetative-to-reproductive transition in Cynara cardunculus by RNA-Seq analysis - A. Paulino; I. Fernandes; R. C. Pires; A. Usié; A. Faustino; J. Santos; T. Brás; D. Rosa; O. S. Paulo; M. F. Duarte; L. Marum (Plant Molecular Biology, 2026)
Cynara cardunculus inflorescence plays a significant role in cheese manufacturing and human consumption due to the milk-clotting capacity and the production of edible immature capitula. Consequently, it is crucial to understand the complex cellular and molecular processes involved in the development of cardoon flowers. The current study used western wild cardoon in two developmental stages, vegetative and reproductive, to understand the molecular mechanisms mediating cardoon`s vegetative-to-reproductive transition. Transcriptome profiling identified 552 differentially expressed genes (DEGs) between vegetative and reproductive stages, with 321 upregulated in stage 4 (vegetative state) and 231 in stages 5/6 (reproductive state). Gene Ontology (GO) analysis revealed DEGs involved in biological processes such as oxidation-reduction, lipid metabolism, and defense responses. Metabolic pathways, including phenylpropanoid biosynthesis and anther/pollen development, were significantly enriched. Genes associated with lignin formation, flavonoid synthesis, and acetyltransferase activity were upregulated in the vegetative stage. At the same time, those related to flower development and sesquiterpene lactone biosynthesis were prominent in the reproductive stage. Transcription factors, including MADS-box and ethylene-responsive families, were critical in regulating developmental transitions. This study provides comprehensive insights into the morphological, chemical, and molecular dynamics of C. cardunculus across its phenological stages, underscoring the plant’s adaptability and potential for pharmaceutical and industrial applications. The findings highlight the importance of seasonal and developmental timing in optimizing the production of valuable secondary metabolites, such as cynaropicrin.

High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

Ionoregulatory and hematological parameters of Triportheus albus populations living in natural white- and blackwaters of the Amazon - Rafael Mendonça Duarte; Susana Braz-Mota; Maria de Nazaré Paula Silva; Guacira de Figueiredo Eufrasio Pauly; João Henrique Alliprandini Costa; Jhonathan da Mota Silva; Adalberto L. Val (Journal of Comparative Physiology B, 2026)
In the Amazon basin, the white- and blackwater rivers have marked variability in their natural physicochemical characteristics, which impose differential physiological constraints that shape aquatic biodiversity. Thriportheus albus is a Characiform fish widely distributed throughout the different types of water in Amazon basin, with two distinct and isolated populations, a whitewater and a blackwater/clearwater population. In this study we compare blood biochemical, hematological parameters and the activity of the main ionoregulatory enzymes in gills and kidneys of T. albus populations from the blackwaters of Rio Negro and in the whitewater’s of Rio Solimões. T. albus from the blackwaters showed a higher hemoglobin concentration, hematocrit and levels of Na and Ca in blood compared to fish from the whitewater. Remarkably, the activity of both Na + /K + -ATPase and NEM sensitive-ATPase were significantly higher in the gills and kidneys of T. albus from blackwater. A Principal Component Analysis (PCA) revealed that up regulation of both transporters were closed related to increased blood parameters in T. albus from blackwater, suggesting that physiological adjustments in mechanisms for ionic uptake in gills and reabsorption in kidney aid fish to avoid internal disturbances in blood ionic levels, and optimize oxygen transport, to cope with the extremely low ionic content and high acidity found in Rio Negro. Altogether, these findings indicate that physiological adjustments in hematological parameters, and in the control of the gills and kidneys functions exert a central role in the adaptation of T. albus to the acidic ion-poor conditions of Amazonian blackwaters.

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Boat noise alters behaviour of two coral reef macroinvertebrates, Lambis lambis and Tridacna maxima - M.N. Havlik; N.R. Geraldi; L.W. Hopkins; J. Hubert; L. Chapuis; L.P. Gaffney; R.P. Wilson; S.D. Simpson; F.J. Juanes; C.M. Duarte (Marine Pollution Bulletin, 2026)

Megabenthic bivalves in the subtidal area of the Gulf of Cádiz (SW Spain): Diversity and assemblages patterns - S. Román; M.M. González-Duarte; A. Rodríguez-Rúa; L. Silva; M. Delgado (Regional Studies in Marine Science, 2025)

Changes in land use and buffaloes trampling effects on soil health in environmentally vulnerable areas of an Atlantic Forest biome in southern São Paulo State, Brazil - Rodrigo Batista Pinto; Francisca Alcivania de Melo Silva; Heitor Marcel da Silva Ribeiro; Pedro Henrique de Oliveira Vilela; Rafael Duarte L'Abbate; Fabiana Gomes da Silva; Diogenes L. Antille; Zigomar Menezes de Souza; Reginaldo Barboza da Silva (Geoderma Regional, 2025)

Geological and geomechanical properties of soft rocks from the Lower Jurassic Vale Das Fontes Formation (Lusitanian Basin, Portugal): an exploratory study - P. F. Moreira; C. F. Rodrigues; L. V. Duarte; J. P. Temporão de Sousa; A. Vega y de La Fuente; A. Maldonado-Zamora; M. J. Lemos de Sousa; H. I. Chaminé (Mediterranean Geoscience Reviews, 2025)

Quantitative summary of nine years of fungicide efficacy data for managing white spot and protecting yield in maize - MonalisaC. De Cól; Karla Braga; AdrianoA.P. Custódio; Marcelo G. Canteri; Lucas H. Fantin; Carlos M. Utiamada; Hércules D. Campos; Dagma D. Silva-Araújo; Rodrigo V. Costa; InêsF.U. Yada; Aildson P. Duarte; Alfredo R. Dias; et al. (Crop Protection, 2025)

Ohmic heating for attenuation of Lactobacillus acidophilus LA-5 in Minas Frescal cheese: probiotic survival, biological activity, and in vitro antimicrobial activity - Cássia P. Barros; Tatiana C. Pimentel; Ramon Silva; Maria Carmela K.H. Duarte; Eliane T. Mársico; Erick A. Esmerino; Pedro Henrique C. Felix; Carlos Augusto F. Oliveira; Beatriz L. Valente; Marcelo Cristianini; Mônica Q. Freitas; Adriano G. Cruz (Food Research International, 2025)

The role of Penicillium brevicompactum in bioprocessing plastic and metals from printed circuit boards - Diogo A. Ferreira-Filipe; Marta Carvalho; António J.S. Fernandes; Florinda M. Costa; Carla Patinha; Pedro Pato; Armando C. Duarte; Teresa Rocha-Santos; Ana L. Patrício Silva (Environmental Pollution, 2025)

Global Patterns and Drivers of Seagrass Biomass, Net Primary Production and Meadow Structure - Nicole R. Foster; Enric Gomis; Diana I. Montemayor; Simone Strydom; Miguel Angel Mateo; Eduard Serrano; Aurora M. Ricart; Martin Dahl; Ines Mazarrasa; Paulina Cisternas; Harry Whiteley; Elliott J. Bates; et al. (Journal of Biogeography, 2025)
Aim We decipher global patterns in seagrass growth and structure to advance seagrass science, facilitate multidisciplinary research, and promote effective management strategies and policy development for seagrass habitats. Location: Global. Time period: 1975 to 2024. Major taxa studied: Seagrasses—marine angiosperms. Methods A global data set on seagrass total biomass, total net primary productivity (NPP), shoot density, and percent cover was compiled across 11 genera. We tested how these variables change across seagrass genera, life‐history strategy, and geographic location; and then modelled the environmental drivers (temperature, nutrients, light availability) of the patterns observed. Results The mean (±SE) total biomass of seagrasses globally was estimated at 340 ± 10 g DW m −2 and total NPP was estimated at 5.4 ± 0.4 g DW m −2 d −1 . Mean shoot density across all genera was 1,780 ± 67 shoots m −2 and percent cover was 42% ± 1%. Persistent genera showed the highest total biomass followed by opportunistic then colonising genera, whereas shoot density was higher for colonising than persistent, which had the highest percent cover. Latitudinal and bioregional patterns were identified for some genera and were mostly driven by genus‐specific traits, followed by localised environmental factors. Main Conclusions Trends in seagrass meadow ecology were largely influenced by seagrass genera and their life‐history strategy, with localised environmental factors, such as temperature and nutrients, also playing a role. Global estimates of seagrass biomass and NPP were 2‐times higher than previously reported. Seagrass life‐history strategies modulate the trade‐offs between NPP and biomass to thrive in specific habitats. This study provides the most updated global synthesis of patterns in seagrass growth and structure.

Sex Drives Intraspecific Scaling of Home Range Size in Mammals - Aline Giroux; Denis Valle; Eliezer Gurarie; Marcus Vinicius Vieira; James D. Forester; Luca Börger; Raissa Sepulvida; Nicole Barbour; Erika G. da Rocha; Julia Oshima; Fernanda C. de Azevedo; Frederico G. Lemos; et al. (Ecology Letters, 2025)
Understanding variation in home range size (HR) provides important insights into the underlying ecological processes driving space use. However, it remains unclear whether the interspecific allometric scaling of mammals' HR can also be consistently observed within species and for both sexes. To address this knowledge gap, we GPS‐tracked 349 resident individuals across Brazil, encompassing 18 mammal species. We estimated individuals' HR and modelled intraspecific variation in HR against body mass (BM) and sex. While males showed a positive allometric scaling similar to interspecific findings reported in the literature (exponent = 1.23), females' BM had no statistically discernible relationship with HR. We suggest that males have greater energetic and evolutionary incentives to expand their HR with increasing BM, and more physical capacity to do so. Traditional studies on HR scaling that disregard individual sex may, in reality, reflect an average of two distinct patterns, while failing to accurately represent either one.

Direct Drivers of Spontaneous Exotic Plant Richness in Southern Patagonia from Argentina - Pablo L. Peri; Brenton Ladd; Romina Lasagno; Sandra Duarte Guardia; María Vanessa Lencinas; Guillermo Martínez Pastur (Current Landscape Ecology Reports, 2025)

Polymorphisms in Hg-related genes and their impact on mercury burden and oxidative stress biomarkers among riverside Amazonian populations - Flora Troina Maraslis; Nathália de Assis Aguilar Duarte; Emilene Arusievicz Nunes; Lindiane Eloisa de Lima; Juliana Mara Serpeloni; Milena Horvat; José L. Domingo; Fernando Barbosa; Gustavo Rafael Mazzaron Barcelos (Chemosphere, 2025)

Assessing the impact of urbanization on wetland bird communities in Chilean Mediterranean coast - Pablo Díaz-Siefer; Isidora Duarte; Victoria Madrid; Natalia Olmos-Moya; Francisco E. Fontúrbel; Juan L. Celis-Diez (Urban Ecosystems, 2025)

Carbon footprint calculator for the Portuguese textile and clothing industry: development, application and validation - C. Duarte; J. V. Ferreira; I. P. L. Brás; M. E. F. Silva (International Journal of Environmental Science and Technology, 2025)
This study aimed to develop, implement, and validate a carbon footprint (CF) calculator to estimate greenhouse gas (GHG) emissions generated by Portugal´s Textile and Clothing Sector (TCS). To achieve this, the GHG Protocol and life cycle assessment (LCA) methodology were applied to develop the CF and analyse two textile and clothing companies (A and B). Validation was conducted using a self-assessment method that employed 2 online calculators and a LCA software. The CF calculator enables the quantification of the 3 scopes of GHG emissions. Scope 1 includes direct emissions from sources that are owned or controlled by the company, such as on-site energy, transportation of raw materials, finished products and personnel, as well as water usage. Scope 2 comprises indirect emissions from the use of purchased energy and Scope 3 includes emissions that occur across the supply chain, such as public water usage, wastewater, transportation, employee business travel, waste disposal and the end-of-life treatment of sold products. Avoided emissions and carbon offsetting measures and carbon sequestration strategies, were included. For Company A, energy consumption was the largest contributor to the CF, accounting for 76% of the contributions. In Company B, the waste component had the greatest impact on the CF, accounted for 38% of the contributions. In the validation process, the electricity and fuel consumption components yielded values that are consistent with those from other calculators. The calculator is a tool that TCS companies can use to quantify their emissions and define measures to reduce or offset their CF.

Comparative analysis of bacterial and microalgal natural astaxanthin: Part II — Biocompatibility, bioaccessibility, encapsulation, mutagenicity, and aquatic toxicity - Cassamo U. Mussagy; Ana L.R. Gini; Cauê B. Scarim; Jonatas L. Duarte; Marlus Chorilli; Gabriely F.G. Militão; Amanda dos Santos; Nayara P. Lima; Isabela S. Ribeiro; Charles W.I. Haminiuk; Fabiane O. Farias; Gisela de A. Umbuzeiro; et al. (Algal Research, 2025)

Geochemical variability of Gryphaea (Ostreoida, Bivalvia) in the upper Sinemurian organic-rich marls and limestones of the Lusitanian Basin (Portugal) - Ricardo L. Silva; Luís V. Duarte; Clemens V. Ullmann; María J. Comas-Rengifo (Journal of Iberian Geology, 2025)

Stability of adenine in interaction with saponite in a simulated hydrothermal impact-generated system and its implications for astrobiology - L. Ramírez-Vázquez; A.A. Duarte-Ruiz; M.G. Santiago-Santos; G. Cordero Tercero; J.A. Cruz-Castañeda (Planetary and Space Science, 2025)

Optimizing wild blueberry juice production: Sensory, physicochemical, and phytochemical characteristics - Alberto Zárate-Carbajal; Sylvie L. Turgeon; Laurent Bazinet; Matthew Mcsweeney; Arturo Duarte Sierra (International Journal of Gastronomy and Food Science, 2025)

Supramolecular environment and androgen receptor binding of taraxerol: from molecular structure to potential bioactivity function - Lara L. G. C. Rodrigues; Vitor S. Duarte; Antônio S. N. Aguiar; Vitória A. M. Silva; Hamilton B. Napolitano; Leonardo L. Borges (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Molecular modeling of a novel butane-substituted chalcone: from synthesis to comprehensive electron density analysis - Aécio V. B. Oliveira; Vitor S. Duarte; Renata Layse. G. de Paula; Jaqueline E. Queiroz; Gilberto L. B. de Aquino; Hamilton B. Napolitano; Ademir J. Camargo (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Molecular modeling of a chlorine chalcone with a potential platelet antiaggregant - Patricia R. S. Wenceslau; Vitor S. Duarte; Antônio S. N. Aguiar; Fernanda S. Fernandes; Guilherme R. Oliveira; Leonardo L. Borges; Hamilton B. Napolitano (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Exploring intra-specific variation in photosynthesis of maize and sorghum - Rafael L. Almeida; Neidiquele M. Silveira; Heitor L. Sartori; Camila C. Carvalho; Maximiliano S. Scarpari; Aildson P. Duarte; Eduardo Sawazaki; Eduardo C. Machado; Rafael V. Ribeiro (Theoretical and Experimental Plant Physiology, 2025)

Novel paramyxovirus in wild pinnipeds, Brazil - Samira Costa-Silva; Ana Carolina Ewbank; Aricia Duarte-Benvenuto; Carlos Sacristán; Rodrigo M. Soares; Angélica M. Sánchez-Sarmiento; Natália Silvestre-Perez; Pedro Volkmer Castilho; Cristiane K. M. Kolesnikovas; Caroline Freitas Pessi; Rafael Sardinha Murro; Carla B. Barbosa; et al. (Veterinary Research Communications, 2025)
Most emerging zoonotic viral infections originate in wildlife. The Paramyxoviridae and Coronaviridae families are important in terms of zoonotic potential and diversity of host susceptibility. To date, the only paramyxoviruses described in pinnipeds are within the genus Morbillivirus . An alphacoronavirus has been reported in pinnipeds. Herein, we surveyed for Paramyxoviridae and Coronaviridae in 46 animals of four pinniped species stranded along the coasts of Santa Catarina and São Paulo states, Brazil, between 2016 and 2022. A novel paramyxovirus (family Paramyxoviridae ) was detected in an Antarctic fur seal ( Arctocephalus gazella ) and in two South American fur seals ( Arctocephalus australis ). The sequences presented with less than 83% amino acid identity to the closest published paramyxovirus sequences, amplified in Microchiroptera sp. in Vietnam and in Asiatic yellow bats ( Scotophilus kuhlii ) in Cambodia. Phylogenetic analysis of the paramyxovirus sequences clustered into the genus Jeilongvirus . Gross and histopathological analyses did not identify any related lesions and the viral zoonotic potential is unknown. None of the animals were PCR-positive to coronavirus. To our knowledge, this is the first report of paramyxovirus infection in pinnipeds in Brazil and the first paramyxovirus not classified as Morbillivirus in seals, sea lions and walruses. To better understand the natural history of this novel virus, future pathological, serological, and molecular studies based on pan- Paramyxoviridae RT-PCRs are recommended.

Societal value of seagrass from historical to contemporary perspectives - Nicole R. Foster; Eugenia T. Apostolaki; Katelyn DiBenedetto; Carlos M. Duarte; David Gregory; Karina Inostroza; Dorte Krause-Jensen; Benjamin L. H. Jones; Eduard Serrano; Rym Zakhama-Sraieb; Oscar Serrano (Ambio, 2025)
Seagrasses have been entwined with human culture for millennia, constituting a natural resource that has supported humanity throughout this history. Understanding the societal value of seagrass fosters appreciation of these ecosystems, encouraging conservation and restoration actions to counteract historic and predicted losses. This study overviews the plethora of seagrass use in human history, ranging from spiritual and ceremonial roles, direct and indirect food resources, medicines and raw materials, dating back more than 180 000 years. While many past uses have been abandoned in modern societies, others have persisted or are being rediscovered, and new applications are emerging. As these uses of seagrasses depend on harvesting, we also underscore the need for sustainable practices to (re)generate positive interactions between seagrasses and society. Our review contributes to revalue seagrass societal ecosystem services, highlighting ancient and more recent human and seagrass relationships to incentivize conservation and restoration actions.

Global Review of Blue Carbon Ecosystem Microbial Communities - Christina Birnbaum; Pawel Waryszak; Stacey M. Trevathan‐Tackett; Jennifer L. Bowen; Rod M. Connolly; Carlos M. Duarte; Peter I. Macreadie (Environmental Microbiology, 2025)
Microbial communities underpin biogeochemical processes in Blue Carbon Ecosystems (BCEs); however, a comprehensive review of geographic patterns in microbial diversity, microbial functions, and distribution is currently lacking. Here, for the first time, we have analysed 70 years (1930–2020) of archaeal, bacterial, and fungal diversity and functions in mangrove, saltmarsh, and seagrass ecosystems to elucidate publication and geographic trends in reporting data in BCEs and to identify knowledge gaps. Of the 649 journal articles analysed, research on BCE microbial communities has focused overwhelmingly on assessing bacterial richness and functions in BCEs. Our gap analysis revealed that only ~25%–50% of the countries that have BCEs have been represented, suggesting that our understanding of archaeal, bacterial, and fungal geographic diversity in BCEs is still incomplete. In the context of taxonomic‐based limitations in our study's approach, we have identified gaps of knowledge in archaeal and fungal sediment biodiversity in saltmarsh and seagrass ecosystems. This significantly impacts our ability to forecast ecosystem services amid current and future human and climate pressures in BCEs. The results from this synthesis could serve as a useful reference for microbial baseline data and research trends in BCEs to develop novel hypothesis‐testing research.

The essential oil of Drimys brasiliensis (Winteraceae) from Atlantic forest as an alternative biopesticide against stored pests and seedborne diseases - Rubens Candido Zimmermann; Carolina Gracia Poitevin; Ana Marta Schafaschek; Milena Ielen; Sofia Bin Macedo; Wanderlei do Amaral; Greissi Tente Giraldi; Edson José Mazarotto; Alessandra Benatto; Carlos Eduardo Nogueira Martins; Beatriz Helena L. N. Sales Maia; Elaine Fernanda Dos Santos; et al. (Biocatalysis and Agricultural Biotechnology, 2025)

Stabilisation and destabilisation of coastal blue carbon: The key factors - Peter I. Macreadie; Anirban Akhand; Stacey M. Trevathan-Tackett; Carlos M. Duarte; Jeff Baldock; Jennifer L. Bowen; Rod M. Connolly (Earth-Science Reviews, 2025)

Highly Efficient Bio-Based Composites from Natural Fibers for Fauna Protection and Oil Spill Remediation - Islla M. C. Silvino; Beatriz S. Alves; Eduardo J. Fonseca; Vanderson B. Bernardo; Carmem L. P. S. Zanta; Josealdo Tonholo; Laís F. A. M. Oliveira; José L. S. Duarte; Leonardo M. T. M. Oliveira (Environmental Processes, 2025)

Alphanudiviral segments found in transcriptomes of the two-spotted spider mite, Tetranychus urticae (Acari: Tetranychidae) - Ethiane Rozo Santos; Jirka Manuel Petersen; Thaís Danielle Duarte Santana; Robert L. Harrison; Daniel M. P. Ardisson-Araújo (Virus Genes, 2025)

Activation of the 20S proteasome core particle prevents cell death induced by oxygen- and glucose deprivation in cultured cortical neurons - Ivan L. Salazar; Michele Curcio; Miranda Mele; Rossela Vetrone; Simone Frisari; Rui O. Costa; Margarida V. Caldeira; Darci J. Trader; Carlos B. Duarte (Apoptosis, 2025)
Neuronal damage in brain ischemia is characterized by a disassembly of the proteasome and a decrease in its proteolytic activity. However, to what extent these alterations are coupled to neuronal death is controversial since proteasome inhibitors were shown to provide protection in different models of stroke in rodents. This question was addressed in the present work using cultured rat cerebrocortical neurons subjected to transient oxygen- and glucose-deprivation (OGD) as a model for in vitro ischemia. Under the latter conditions there was a time-dependent loss in the proteasome activity, determined by cleavage of the Suc-LLVY-AMC fluorogenic substrate, and the disassembly of the proteasome, as assessed by native-polyacrylamide gel electrophoresis followed by western blot against Psma2 and Rpt6, which are components of the catalytic core and regulatory particle, respectively. Immunocytochemistry experiments against the two proteins also showed differential effects on their dendritic distribution. OGD also downregulated the protein levels of Rpt3 and Rpt10, two components of the regulatory particle, by a mechanism dependent on the activity of NMDA receptors and mediated by calpains. Activation of the proteasome activity, using an inhibitor of USP14, a deubiquitinase enzyme, inhibited OGD-induced cell death, and decreased calpain activity as determined by analysis of spectrin cleavage. Similar results were obtained in the presence of two oleic amide derivatives (B12 and D3) which directly activate the 20S proteasome core particle. Together, these results show that proteasome activation prevents neuronal death in cortical neurons subjected to in vitro ischemia, indicating that inhibition of the proteasome is a mediator of neuronal death in brain ischemia.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Non-phytotoxic compounds of Baccharis from the Atlantic Forest as a sustainable alternative for controlling stored-wheat fungi - Camila Eccel; Rubens Candido Zimmermann; Edson José Mazarotto; Carolina Gracia Poitevin; Wanderlei Do Amaral; Greissi Tente Giraldi; Beatriz Helena L. N. Sales Maia; Elaine Fernanda Dos Santos; Henrique Da Silva Silveira Duarte; Carlos Eduardo Nogueira Martins (Environmental Science and Pollution Research, 2025)

Biological activity of essential oil from Piper mikanianum leaves and its major compound against storage pests and fungi - Rafael Sari; Rubens Candido Zimmermann; Carolina Gracia Poitevin; Edson José Mazarotto; Carlos Eduardo Nogueira Martins; Henrique da Silva Silveira Duarte; Ricardo Andrade Rebelo; Beatriz Helena L. N. Sales Maia (Environmental Science and Pollution Research, 2025)

Monitoring the stability of aerobic granular sludge under increasing fractions of slowly biodegradable substrate using quantitative image analysis - Sérgio A. Silva; M. Salomé Duarte; António L. Amaral; Eugénio C. Ferreira; M. Madalena Alves; Daniela P. Mesquita (Chemosphere, 2025)

Evaluation of rapid evaporative ionization mass spectrometry (REIMS) for the prediction of slice shear force and quality grades in beef longissimus lumborum steaks - Kaitlyn R. Loomas; Dale R. Woerner; Ben M. Bohrer; Tyson R. Brown; Heather L. Bruce; Marcio S. Duarte; Bimol C. Roy; Yifei Wang; Katie Pedgerachny; Jerrad F. Legako (Meat Science, 2025)

Ingestive behaviour, performance, and methane emissions of pregnant alpacas grazing cultivated pastures in the high Peruvian Andes - Laura B. Gualdrón-Duarte; Cecilia Loza; José I. Gere; Nancy F. Huanca-Marca; Francisco E. Franco; Yemi Sanca Uscamayta; Rubén García‐Ticllacuri; Guadalupe Orellana Ligas; Diannett Benito López; Feliciano Rivera Pachiño; Juan E. Moscoso-Muñoz; Medardo A. Díaz-Céspedes; et al. (Livestock Science, 2025)

A Cross Biome Synthesis on Pollination Systems in a Megadiverse Tropical Country - Lorena B. Valadão-Mendes; Renata Trevizan; Mariana O. Duarte; Victor H. D. Silva; Marsal D. de Amorim; Camila S. Souza; Pietro K. Maruyama; Alberto L. Teixido (The Botanical Review, 2025)

Empowering informed choices: How computer vision can assists consumers in making decisions about meat quality - Guilherme L. Menezes; Dante T. Valente Junior; Rafael E.P. Ferreira; Dario A.B. Oliveira; Julcimara A. Araujo; Marcio Duarte; Joao R.R. Dorea (Meat Science, 2025)

Synthesis and Characterization of a Magnetic TiO2 for Propylparaben Degradation - Amanda L. M. S. Melo; Filipe S. Duarte; Alice B. Ferro; Rayssa J. B. Motta; Carmem L. P. S. Zanta; Leonardo M. T. M. Oliveira; José L. S. Duarte; Rosane M. P. B. Oliveira (Water, Air, & Soil Pollution, 2025)

Anthocyanins stabilization of Hibiscus sabdariffa extract with sepiolite: Analytical and reactive force fields approaches - Ana S. Márquez-Rodríguez; Arasay Carrión; Felipe Trejo; Hilda E. Esparza-Ponce; José M. Nápoles-Duarte; María L. Ballinas-Casarrubias; Luis E. Fuentes-Cobas; Erika Salas; Juan P. Palomares-Báez; María E. Fuentes-Montero (Sustainable Chemistry and Pharmacy, 2024)

Residential relocation and changes in patterns of environmental exposures by health determinants among children and adolescents in Catalonia, Spain - A. Pistillo; S. Warkentin; A. Abellan; J. de Bont; T. Ranger; L. Pérez-Crespo; M. Cirach; A. Perramon-Malavez; S. Khalid; M. Nieuwenhuijsen; M. Vrijheid; T. Duarte-Salles (Environmental Research, 2024)

Extraction and Purification of Biopolymers from Marine Origin Sources Envisaging Their Use for Biotechnological Applications - Duarte Nuno Carvalho; Cristiana Gonçalves; Rita O. Sousa; Rui L. Reis; J. Miguel Oliveira; Tiago H. Silva (Marine Biotechnology, 2024)
Biopolymers are a versatile and diverse class of materials that has won high interest due to their potential application in several sectors of the economy, such as cosmetics, medical materials/devices, and food additives. In the last years, the search for these compounds has explored a wider range of marine organisms that have proven to be a great alternative to mammal sources for these applications and benefit from their biological properties, such as low antigenicity, biocompatibility, and biodegradability, among others. Furthermore, to ensure the sustainable exploitation of natural marine resources and address the challenges of 3R’s policies, there is a current necessity to valorize the residues and by-products obtained from food processing to benefit both economic and environmental interests. Many extraction methodologies have received significant attention for the obtention of diverse polysaccharides, proteins, and glycosaminoglycans to accomplish the increasing demands for these products. The present review gives emphasis to the ones that can be obtained from marine biological resources, as agar/agarose, alginate and sulfated polysaccharides from seaweeds, chitin/chitosan from crustaceans from crustaceans, collagen, and some glycosaminoglycans such as chondroitin sulfate and hyaluronic acids from fish. It is offered, in a summarized and easy-to-interpret arrangement, the most well-established extraction and purification methodologies used for obtaining the referred marine biopolymers, their chemical structure, as well as the characterization tools that are required to validate the extracted material and respective features. As supplementary material, a practical guide with the step-by-step isolation protocol, together with the various materials, reagents, and equipment, needed for each extraction is also delivered is also delivered. Finally, some remarks are made on the needs still observed, despite all the past efforts, to improve the current extraction and purification procedures to achieve more efficient and green methodologies with higher yields, less time-consuming, and decreased batch-to-batch variability. Graphical Abstract

Predicting health impacts of wildfire smoke in Amazonas basin, Brazil - Yara de Souza Tadano; Sanja Potgieter-Vermaak; Hugo Valadares Siqueira; Judith J. Hoelzemann; Ediclê S.F. Duarte; Thiago Antonini Alves; Fabio Valebona; Iuri Lenzi; Ana Flavia L. Godoi; Cybelli Barbosa; Igor O. Ribeiro; Rodrigo A.F. de Souza; et al. (Chemosphere, 2024)

Mapping high-risk areas for Mycobacterium tuberculosis complex bacteria transmission: Linking host space use and environmental contamination - Eduardo M. Ferreira; Mónica V. Cunha; Elsa L. Duarte; António Mira; Daniela Pinto; Inês Mendes; André C. Pereira; Tiago Pinto; Pelayo Acevedo; Sara M. Santos (Science of The Total Environment, 2024)

Blood levels of 21 metals and metalloids in riverside villagers of the Brazilian Amazon: A human biomonitoring study with associations with sociodemographic, dietary, and lifestyle factors - Jonas Carneiro Cruz; Lucas Cassulatti dos Santos; Paula Pícoli Devoz; Matheus Gallimberti; Gabriel Neves Cerazette; Nathália de Assis Aguilar Duarte; Lindiane Eloísa de Lima; Emilene Arusievicz Nunes; Johnnasson de Medeiros Soares; Maria Laise dos Santos Pinto; Geovanna da Silva Soares; Suelen Santos de Souza; et al. (Environmental Research, 2024)

Exposing illegal hunting and wildlife depletion in the world's largest tropical country through social media data - Hani R. El Bizri; Marcela A. Oliveira; Aline Pessutti Rampini; Simon Knoop; Julia E. Fa; Lauren Coad; Thais Queiroz Morcatty; Gabriel Favero Massocato; Arnaud L. J. Desbiez; João Vitor Campos‐Silva; Daniel Zani La Laina; José Maurício Barbanti Duarte; et al. (Conservation Biology, 2024)
Globally, illegal sport hunting can threaten prey populations when unregulated. Due to its covert nature, illegal sport hunting poses challenges for data collection, hindering efforts to understand the full extent of its impacts. We gathered social media data to analyze patterns of illegal sport hunting and wildlife depletion across Brazil. We collected data for 2 years (2018–2020) across 5 Facebook groups containing posts depicting pictures of illegal sport hunting events of native fauna. We described and mapped these hunting events by detailing the number of hunters involved, the number of species, the mean body mass of individuals, and the number and biomass of individuals hunted per unit area, stratified by Brazilian biome. We also examined the effects of defaunation on hunting yield and composition via regression models, rank–abundance curves, and spatial interpolation. We detected 2046 illegal sport hunting posts portraying the hunting of 4658 animals (∼29 t of undressed meat) across all 27 states and 6 natural biomes of Brazil. Of 157 native species targeted by hunters, 19 are currently threatened with extinction. We estimated that 1414 hunters extracted 3251 kg/million km 2 . Some areas exhibited more pronounced wildlife depletion, in particular the Atlantic Forest and Caatinga biomes. In these areas, there was a shift from large mammals and reptiles to small birds as the main targeted taxa, and biomass extracted per hunting event and mean body mass across all taxonomic groups were lower than in other areas. Our results highlight that illegal sport hunting adds to the pressures of subsistence hunting and the wild meat trade on Brazil's wildlife populations. Enhanced surveillance efforts are needed to reduce illegal sport hunting levels and to develop well‐managed sustainable sport hunting programs. These can support wildlife conservation and offer incentives for local communities to oversee designated sport hunting areas.

P14-06 The cytotoxicity of bortezomib in AC16 cardiac cells and possible therapeutic options involving Nrf2 - C. Vitorino-Oliveira; S. Kahremany; L. Nisim; M. Duarte-Araújo; F. Carvalho; A. Gruzman; V.M. Costa (Toxicology Letters, 2024)

P13-31 Characterization of human isogenic epithelial cell lines as a relevant tool to study colon carcinogenesis and interaction between genes and environment - A. Tête; L. Arnaud; H. Le Mentec; N. Poupin; I. Gallais; N. Tournade; C. Duarte Hospital; Y. Lippi; F. Mathevet; C. Pilati; G. Lefort; C. Lavau; et al. (Toxicology Letters, 2024)

P13-18 Succinate Dehydrogenase inhibitors (SDHi) fungicides induce mitochondrial dysfunction and metabolic reprogramming in human colon cells - C. Duarte-Hospital; A. Tête; K. Debizet; C. Rives; J. Imler; L. Galès; F. Bellvert; J. Dairou; R. Barouki; J.W. Shay; J. Bastin; S. Mouillet-Richard; et al. (Toxicology Letters, 2024)

Magnetic refrigeration enhanced by magnetically-activated thermal switch: An experimental proof-of-concept - Vivian M. Andrade; Cláudia R. Fernandes; Daniel J. Silva; Joana S. Teixeira; Clara R. Pereira; Rita Duarte; Ana L. Pires; João Ventura; Joana Oliveira (International Journal of Refrigeration, 2024)

Weather ageing effects on the long-term thermal conductivity and biological colonisation of thermal insulating mortars with EPS, cork and aerogel - Léo Pinchard; João L. Parracha; Rosário Veiga; Luís Matias; António Santos Silva; Sónia Duarte; Lina Nunes (Energy and Buildings, 2024)

Bacterial septicemia and herpesvirus infection in Antarctic fur seals (Arctocephalus gazella) stranded in the São Paulo coast, Brazil - Aricia Duarte-Benvenuto; A. M. Sánchez-Sarmiento; A. C. Ewbank; R. Zamana-Ramblas; S. Costa-Silva; N. Silvestre; T. Faita; L. B. Keid; R. M. Soares; C. F. Pessi; J. R. Sabbadini; M. F. Borges; et al. (Veterinary Research Communications, 2024)
In August 2021, two juvenile male Antarctic fur seals ( Arctocephalus gazella ) stranded in the southeastern Brazilian coast and were referred to rehabilitation centers. The animals presented increased body temperature, prostration, respiratory distress and despite treatment died. A necropsy following a standardized protocol was performed, and formalin-fixed tissues were processed for microscopic examination. Samples were screened for morbillivirus, herpesvirus, and Brucella spp. by molecular analyses (PCR, RT-PCR). Bacteriological culture was performed in samples collected from the lungs, trachea, and lymph nodes of both cases. The main histopathologic findings were of infectious nature, including multifocal necrotizing and fibrinous mixed interstitial pneumonia, bronchiolitis, and bronchitis, with intralesional myriad bacteria associated with vascular fibrinoid necrosis. Pseudomonas aeruginosa was isolated from tracheal and lung swabs of Case 1, and Klebsiella oxytoca was found in nostril swabs, tracheobronchial lymph nodes, and lung of Case 2. Gammaherpesvirus infection was detected in both cases, and the sequences retrieved were classified into the genus Percavirus . All tested samples were PCR-negative for Brucella spp. and morbillivirus. We hypothesize that the deficient immunological status in association with starvation predisposed the reactivation of herpesvirus and secondary bacterial co-infections. To the authors’ knowledge, this is the first molecular detection of herpesvirus in an Antarctic pinniped. These findings reinforce that Otariid gammaherpesvirus circulating in the Southern Hemisphere are likely endemic in the Arctocephalus genus. This report contributes to the current knowledge of health aspects affecting wild pinnipeds, especially in the poorly studied Antarctic species.

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Biodegradation of e-waste microplastics by Penicillium brevicompactum - Diogo A. Ferreira-Filipe; Leila Oliveira; Ana Paço; António J.S. Fernandes; Florinda M. Costa; Armando C. Duarte; Teresa Rocha-Santos; Ana L. Patrício Silva (Science of The Total Environment, 2024)

Neurotoxicology of dopamine: Victim or assailant? - Meghan L. Bucher; Jocelyn Dicent; Carolina Duarte Hospital; Gary W. Miller (NeuroToxicology, 2024)

Interplay between diphenyl diselenide and copper: Impact on D. melanogaster survival, behavior, and biochemical parameters - G.S. Rieder; T. Duarte; C.P. Delgado; A. Rodighiero; P.A. Nogara; L. Orian; M. Aschner; C.L. Dalla Corte; J.B.T. Da Rocha (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Age exacerbates the negative effect of depression on executive functioning in racial and ethnic minorities - Zhimei Niu; Andreana P. Haley; Alexandra L. Clark; Audrey Duarte (Brain Imaging and Behavior, 2024)
Age and depression may interact to produce a “double jeopardy” for cognitive impairment, and executive functioning, in cognitively unimpaired aging. Few studies have considered middle age or the ethnoracial diversity of subjects, despite evidence of more severe cognitive outcomes in historically minoritized people. In this pilot study, we investigated the impact of age on depression-related cognitive impairment and the underlying brain volumes in middle-aged non-Hispanic White adults (116), and Hispanic and Black adults (60), with a total number of 176 adults. The result shows a significant interaction between age and depression for executive functioning, specifically for middle-aged Hispanic and Black adults, but not non-Hispanic White adults. Prefrontal cortex volumes, which were reduced in the Black and Hispanic compared to the non-Hispanic White adults, partially mediated the relationship between depression level and executive functioning, across age and ethnoracial group. Collectively, these results suggest that the negative impact of depression on executive functioning and Prefrontal cortex volumes integrity may be exacerbated by age and that historically minoritized people may be particularly sensitive to this double jeopardy.

Freezing and thawing in Antarctica: characterization of antifreeze protein (AFP) producing microorganisms isolated from King George Island, Antarctica - J. C. Lopes; V. P. Veiga; B. Seminiuk; L. O. F. Santos; A. M. C. Luiz; C. A. Fernandes; C. T. Kinasz; V. H. Pellizari; R. T. D. Duarte (Brazilian Journal of Microbiology, 2024)

Antimicrobial prophylaxis in companion animal surgery: A scoping review for European Network for Optimization of Antimicrobial Therapy (ENOVAT) guidelines - T.M. Sørensen; K. Scahill; J. Espinel Ruperez; M. Olejnik; F. Swinbourne; D.R. Verwilghen; M.C. Nolff; S. Baines; C. Marques; A. Vilen; E.L. Duarte; M. Dias; et al. (The Veterinary Journal, 2024)

The impact of chronic and acute problems on sea turtles: The consequences of the oil spill and ingestion of anthropogenic debris on the tropical semi-arid coast of Ceará, Brazil - Alice F. Feitosa; Ícaro B.H.M.P. Menezes; Oscar S. Duarte; Carminda S．B． Salmito-Vanderley; Pedro B.M. Carneiro; Rufino N.A. Azevedo; André H.B. Oliveira; Ana C.S. Luz; Adriana P. Nascimento; Ronaldo F. Nascimento; Laercio L. Martins; Rivelino M. Cavalcante; et al. (Aquatic Toxicology, 2024)

Microplastics from agricultural mulch films: Biodegradation and ecotoxicity in freshwater systems - Diogo A. Ferreira-Filipe; Ana Paço; Bruna Pinho; Rafael Silva; Sara A.M. Silva; Fátima Jesus; Joana L. Pereira; Armando C. Duarte; Teresa A.P. Rocha-Santos; Ana L. Patrício-Silva (Science of The Total Environment, 2024)

Fibrinonecrotic enteritis and orchitis associated with Salmonella enterica subsp houtenae infection in a short-tailed boa (Boa constrictor amarali) - Raquel M. de Freitas Pereira; Hodias S. de Oliveira Filho; José L. C. Duarte; Fabiano R. P. Júnior; Telma de Sousa Lima; Kin M.O.L. dos Santos; Edivaldo da Silva Pereira; Nádyra Jerônimo da Silva; Celso J. Bruno de Oliveira; Jeann Leal de Araújo; Fábio de Souza Mendonça (Journal of Comparative Pathology, 2024)

Atmospheric microfibrous deposition over the Eastern Red Sea coast - Anastasiia Martynova; Luca Genchi; Sergey P. Laptenok; Michael Cusack; Georgiy L. Stenchikov; Carlo Liberale; Carlos M. Duarte (Science of The Total Environment, 2024)

The biotic ligand model as a promising tool to predict Cu toxicity in amazon blackwaters - Rafael M. Duarte; Anne Crémazy; Chris M. Wood; Vera M.F. Almeida-Val; Adalberto L. Val (Environmental Pollution, 2024)

Higher temperature, increased CO 2 , and changing nutrient ratios alter the carbon metabolism and induce oxidative stress in a cosmopolitan diatom - Hugo Duarte Moreno; Sebastian Rokitta; Nelly Tremblay; Maarten Boersma; Elisabeth Groß; Helena C. L. Klip; Karen H. Wiltshire; Cédric L. Meunier (Limnology and Oceanography, 2024)
Phytoplankton are responsible for about 90% of the oceanic primary production, largely supporting marine food webs, and actively contributing to the biogeochemical cycling of carbon. Yet, increasing temperature and p CO 2 , along with higher dissolved nitrogen: phosphorus ratios in coastal waters are likely to impact phytoplankton physiology, especially in terms of photosynthetic rate, respiration, and dissolved organic carbon (DOC) production. Here, we conducted a full‐factorial experiment to identify the individual and combined effects of temperature, p CO 2 , and N : P ratio on the antioxidant capacity and carbon metabolism of the diatom Phaeodactylum tricornutum . Our results demonstrate that, among these three drivers, temperature is the most influential factor on the physiology of this species, with warming causing oxidative stress and lower activity of antioxidant enzymes. Furthermore, the photosynthetic rate was higher under warmer conditions and higher p CO 2 , and, together with a lower dark respiration rate and higher DOC exudation, generated cells with lower carbon content. An enhanced oceanic CO 2 uptake and an overall stimulated microbial loop benefiting from higher DOC exudation are potential longer‐term consequences of rising temperatures, elevated p CO 2 as well as shifted dissolved N : P ratios.

Facemasks: An insight into their abundance in wetlands, degradation, and potential ecotoxicity - Ana Paço; Ana M. Oliveira; Diogo A. Ferreira-Filipe; Andreia C.M. Rodrigues; Rui J.M. Rocha; Amadeu M.V.M. Soares; Armando C. Duarte; Ana L. Patrício Silva; Teresa Rocha-Santos (Science of The Total Environment, 2023)

APGW/AKH Precursor from Rotifer Brachionus plicatilis and the DNA Loss Model Explain Evolutionary Trends of the Neuropeptide LWamide, APGWamide, RPCH, AKH, ACP, CRZ, and GnRH Families - Cristian E. Cadena-Caballero; Nestor Munive-Argüelles; Lina M. Vera-Cala; Carlos Barrios-Hernandez; Ruben O. Duarte-Bernal; Viviana L. Ayus-Ortiz; Luis A. Pardo-Díaz; Mayra Agudelo-Rodríguez; Lola X. Bautista-Rozo; Laura R. Jimenez-Gutierrez; Francisco Martinez-Perez (Journal of Molecular Evolution, 2023)
In the year 2002, DNA loss model (DNA-LM) postulated that neuropeptide genes to emerged through codons loss via the repair of damaged DNA from ancestral gene namely Neuropeptide Precursor Predictive ( NPP ), which organization correspond two or more neuropeptides precursors evolutive related. The DNA-LM was elaborated according to amino acids homology among LWamide, APGWamide, red pigment-concentrating hormone (RPCH), adipokinetic hormones (AKHs) and in silico APGW/RPCH NPP APGW/AKH NPP were proposed. With the above principle, it was proposed the evolution of corazonin (CRZ), gonadotropin-releasing hormone (GnRH), AKH, and AKH/CRZ (ACP), but any NPP never was considered. However, the evolutive relation via DNA-LM among these neuropeptides precursors not has been established yet. Therefore, the transcriptomes from crabs Callinectes toxotes and Callinectes arcuatus were used to characterized ACP and partial CRZ precursors, respectively. BLAST alignment with APGW/RPCH NPP and APGW/AKH NPP allow identified similar NPP in the rotifer Brachionus plicatilis and other invertebrates. Moreover, three bioinformatics algorithms and manual verification were used to purify 13,778 sequences, generating a database with 719 neuropeptide precursors. Phylogenetic trees with the DNA-LM parameters showed that some ACP, CRZ, AKH2 and two NPP share nodes with GnRH from vertebrates and some of this neuropeptide had nodes in invertebrates. Whereas the phylogenetic tree with standard parameters do not showed previous node pattern. Robinson-Foulds metric corroborates the differences among phylogenetic trees. Homology relationship showed four putative orthogroups; AKH4, CRZ, and protostomes GnRH had individual group. This is the first demonstration of NPP in species and would explain the evolution neuropeptide families by the DNA-LM.

Microbiological aspects of dewatering sewage sludge by removing extracellular polymeric substances during the bioleaching process: a review - J. Gonçalves; L. P. do Nascimento; I. C. S. Duarte (International Journal of Environmental Science and Technology, 2023)

Fishery Closures, More Than Predator Release, Increased Persistence of Nearshore Fishes and Invertebrates to the Deepwater Horizon Oil Spill - Kiva L. Oken; Kenneth W. Able; Kim de Mutsert; F. Joel Fodrie; Paola C. López-Duarte; Charles W. Martin; Michael J. McCann; Jill A. Olin; Michael J. Polito; Brian J. Roberts; Olaf P. Jensen (Estuaries and Coasts, 2023)

Adjacent and downstream effects of forest harvest on the distribution and abundance of larval headwater stream amphibians in the Oregon Coast Range - Adam Duarte; Nathan D. Chelgren; Jennifer C. Rowe; Christopher A. Pearl; Sherri L. Johnson; Michael J. Adams (Forest Ecology and Management, 2023)

Green Nanobioinsecticide of a Brazilian endemic plant for the Aedes aegypti control - V.C.R. Viana; F.P. Machado; R. Esteves; J.A.D. Duarte; J.J.S. Enríquez; M.L.M. Campaz; E.E. Oliveira; M.G. Santos; E. Ricci-Junior; B.M. Ruppelt; L. Rocha (Sustainable Chemistry and Pharmacy, 2023)

Leveraging machine learning algorithms to advance low-cost air sensor calibration in stationary and mobile settings - An Wang; Yuki Machida; Priyanka deSouza; Simone Mora; Tiffany Duhl; Neelakshi Hudda; John L. Durant; Fábio Duarte; Carlo Ratti (Atmospheric Environment, 2023)

Current knowledge on the presence, biodegradation, and toxicity of discarded face masks in the environment - Ana M. Oliveira; Ana L. Patrício Silva; Amadeu M.V.M. Soares; Damià Barceló; Armando C. Duarte; Teresa Rocha-Santos (Journal of Environmental Chemical Engineering, 2023)

Norfloxacin prophylaxis effect on multidrug resistance in patients with cirrhosis and bacterial infections - Sebastián Marciano; Maria N. Gutierrez-Acevedo; Sabrina Barbero; Lorena del C. Notari; Marina Agozino; Jose L. Fernandez; Maria M. Anders; Nadia Grigera; Florencia Antinucci; Orlando F. Orozco Ganem; Maria D. Murga; Daniela Perez; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Genomic insight into iron acquisition by sulfate-reducing bacteria in microaerophilic environments - Larry L. Barton; Americo G. Duarte; Lucian C. Staicu (BioMetals, 2023)

Brain damage serum biomarkers induced by COVID-19 in patients from northeast Brazil - Ryan C. Silva; Michelle M. da Rosa; Heloísa I. Leão; Eduardo D. L. Silva; Nathália T. Ferreira; Amanda P. B. Albuquerque; Gisele S. Duarte; André M. Siqueira; Michelly C. Pereira; Moacyr J. B. M. Rêgo; Maira G. R. Pitta (Journal of NeuroVirology, 2023)

Amazon raw clay as a precursor of a clay-based adsorbent: experimental study and DFT analysis for the adsorption of Basic Yellow 2 dye - Emanuele D. V. Duarte; Wedja T. Vieira; Rodrigo O. Góes; Luiz E. C. de Azevedo; Melissa G. A. Vieira; Meuris G. C. da Silva; Samira M. L. de Carvalho (Environmental Science and Pollution Research, 2023)

Probing cellulose–solvent interactions with self-diffusion NMR: Onium hydroxide concentration and co-solvent effects - B. Medronho; A. Pereira; H. Duarte; L. Gentile; A.M. Rosa da Costa; A. Romano; U. Olsson (Carbohydrate Polymers, 2023)

Saponite-inspired Materials as Remediation Technologies for Water Treatment: an Overview - Dihêgo Henrique L. Damacena; Pollyana Trigueiro; Victor Hugo Monteiro; Luzia Maria C. Honorio; Thiago Marinho Duarte; Robson Cunha; Marcelo B. Furtini; Maria Gardennia Fonseca; Edson C da Silva-Filho; Josy A. Osajima (Environmental Processes, 2023)

Quantification of SARS-CoV-2 in wastewater samples from hospitals treating COVID-19 patients during the first wave of the pandemic in Brazil - Juliana Calábria de Araújo; Camila L. Madeira; Thiago Bressani; Cíntia Leal; Deborah Leroy; Elayne C. Machado; Luyara A. Fernandes; Maria Fernanda Espinosa; Gabriel Tadeu O. Freitas; Thiago Leão; Vera Tainá Mota; Alyne Duarte Pereira; et al. (Science of The Total Environment, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Removing chemical and biological pollutants from swine wastewater through constructed wetlands aiming reclaimed water reuse - Maria L. Bôto; Sofia M. Dias; Rute Duarte Crespo; Ana P. Mucha; C. Marisa R. Almeida (Journal of Environmental Management, 2023)

Group or individual housing does not reduce socio-sexual and reproductive responses in anestrous goats during the first contact with the photo-stimulated buck - F.J. González; L. Sifuentes; R. Ulloa-Arvizu; M.J. Palomo Peiró; G. Duarte; I.G. Fernández (Domestic Animal Endocrinology, 2023)

Bioactive compounds from marine macroalgae in the treatment and prevention of neurodegenerative diseases - M. Fernanda C. Leal; Rúben J. G. Duarte; Inês L. Cardoso; Rita I. L. Catarino; Adriana M. Pimenta; M. Renata S. Souto (Neurophysiology, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Speciation process on Brazilian continental islands, with the description of a new insular lancehead of the genus Bothrops (Serpentes, Viperidae) - Fausto E. Barbo; William W. Booker; Marcelo R. Duarte; Betina Chaluppe; José A. Portes-Junior; Francisco L. Franco; Felipe G. Grazziotin (Systematics and Biodiversity, 2022)

Influence of temperature on the toxicity of the elutriate from a pesticide contaminated soil to two cladoceran species - Livia Pitombeira de Figueirêdo; Danillo B. Athayde; Thandy Junio da Silva Pinto; Michiel A. Daam; Glauce da Silva Guerra; Paulo José Duarte-Neto; Evaldo L. G. Espíndola (Ecotoxicology, 2022)

COVID-19: impact on Public Health and hypothesis-driven investigations on genetic susceptibility and severity - Susana David; Guillermo Dorado; Elsa L. Duarte; Stephanie David-Bosne; João Trigueiro-Louro; Helena Rebelo-de-Andrade (Immunogenetics, 2022)

Lionfish on the loose: Pterois invade shallow habitats in the tropical southwestern Atlantic - Marcelo O. Soares; Caroline V. Feitosa; Tatiane M. Garcia; Kelly Ferreira Cottens; Bruno Vinicius; Sandra Vieira Paiva; Oscar de Sousa Duarte; Lívio Moreira Gurjão; Grasielle Dayse de Vasconcelos Silva; Rafaela Camargo Maia; Diego M. Previatto; Pedro B. M. Carneiro; et al. (Frontiers in Marine Science, 2022)
Lionfish ( Pterois spp.) evolved in the Indo-Pacific with predators and prey and invaded regions (e.g., the Caribbean Sea and Mediterranean) where no such balance yet exists. In 2020, four lionfish were recorded on mesophotic reefs of the Amazon offshore Coast and Fernando de Noronha Archipelago. However, until now, there were no records of invasive lionfish in Brazilian nearshore waters or even such a high number of individuals. In this article, we report the continuing invasion process along the Brazilian Province by multiple sightings (72) of lionfish from March to May 2022 in estuaries, seagrass beds, and artificial and natural reefs across 240 km of the Brazilian coast. These are the first records of lionfish in coastal northeast Brazil and the shallowest records (1–16 m) from South Atlantic tropical waters. The largest simultaneous records of lionfish in breakwaters, fishing weirs, and marambaias (artificial reefs used as fishing grounds) on the Brazilian Northeastern coast indicate that these man-made structures are suitable habitats for this species. Most of the lionfish (58%) were recorded in artificial reefs and fishing weirs. Moreover, the detection of invasions in marginal reefs, estuaries, and two marine protected areas characterized by moderately turbid water and high sedimentation rates highlights the adaptability of the lionfish, making it extremely difficult for divers and fishers to capture them. We call for an urgent management plan considering that the invaded tropical region hosts a high level of endemism, and rare and/or cryptic taxa, which increases the risk of impacts since these are primary lionfish prey.

The most extreme heat waves in Amazonia happened under extreme dryness - Duarte F. Costa; Helber B. Gomes; Maria Cristina L. Silva; Liming Zhou (Climate Dynamics, 2022)

Editorial: Emerging Topics in Coastal and Transitional Ecosystems: Science, Literacy, and Innovation - Bernardo Duarte; Célia M. Teixeira; Irene Martins; Aschwin H. Engelen; Raquel L. Costa; Janine Barbara Adams; Maria João Bebianno; Ricardo A. Melo; Vanessa F. Fonseca (Frontiers in Marine Science, 2022)

Accounting for temporal change in multiple biodiversity patterns improves the inference of metacommunity processes - Laura Melissa Guzman; Patrick L. Thompson; Duarte S. Viana; Bram Vanschoenwinkel; Zsófia Horváth; Robert Ptacnik; Alienor Jeliazkov; Stéphanie Gascón; Pieter Lemmens; Maria Anton‐Pardo; Silke Langenheder; Luc De Meester; et al. (Ecology, 2022)
In metacommunity ecology, a major focus has been on combining observational and analytical approaches to identify the role of critical assembly processes, such as dispersal limitation and environmental filtering, but this work has largely ignored temporal community dynamics. Here, we develop a “virtual ecologist” approach to evaluate assembly processes by simulating metacommunities varying in three main processes: density‐independent responses to abiotic conditions, density‐dependent biotic interactions, and dispersal. We then calculate a number of commonly used summary statistics of community structure in space and time and use random forests to evaluate their utility for inferring the strength of these three processes. We find that (i) both spatial and temporal data are necessary to disentangle metacommunity processes based on the summary statistics we test, and including statistics that are measured through time increases the explanatory power of random forests by up to 59% compared to cases where only spatial variation is considered; (ii) the three studied processes can be distinguished with different descriptors; and (iii) each summary statistic is differently sensitive to temporal and spatial sampling effort. Including repeated observations of metacommunities over time was essential for inferring the metacommunity processes, particularly dispersal. Some of the most useful statistics include the coefficient of variation of species abundances through time and metrics that incorporate variation in the relative abundances (evenness) of species. We conclude that a combination of methods and summary statistics is probably necessary to understand the processes that underlie metacommunity assembly through space and time, but we recognize that these results will be modified when other processes or summary statistics are used.

Learning From the Study Fleet: Maintenance of a Large-Scale Reference Fleet for Northeast U.S. Fisheries - Andrew W. Jones; Katie A. Burchard; Anna M. Mercer; John J. Hoey; Michael D. Morin; Giovanni L. Gianesin; Jacob A. Wilson; Calvin R. Alexander; Brooke A. Lowman; Debra G. Duarte; David Goethel; James Ford; et al. (Frontiers in Marine Science, 2022)
Logbook data from commercial fisheries are a vital component in the machinery of management, including tracking the volume of catches and allocating catch spatially. At the same time, logbooks can provide a unique window into the ecological and sociological conditions in marine fisheries, where fishermen interact with marine species and environments frequently and broadly. Traditional logbooks, however, often are not sufficiently standardized (when personal logs), or lack the detail (when regulatory documents) required to adequately understand fisheries ecosystems. The Study Fleet program, operated by the Northeast Fisheries Science Center’s Cooperative Research Branch, was developed to address these shortfalls by engaging members of the fishing industry in collecting high-resolution catch, effort, and environmental data using electronic logbooks. Since its inception, the Study Fleet has expanded from a small project focused on collecting detailed catch information from the New England multispecies groundfish fishery to a program with a wider scope encompassing a variety of fisheries, gears, and environmental parameters from North Carolina to Maine U.S. Over the years, a number of lessons have been learned about recruiting and supporting industry partners, managing the data, evolving technical specifications, and the challenges associated with analyzing and applying self-reported fisheries data. Here we describe the current state of the program and provide summaries of the Study Fleet program operations and outcomes from 2007-2020, with an eye towards successes, challenges, and applicability of the approach in other regions. We suggest other reference fleet programs, as well as other developing fishery dependent data collections (e.g., electronic monitoring programs), develop detailed roadmaps for each data collection to keep participants engaged as collaborators, target specific fisheries to keep resources from being stretched too thin, and partner with data users early. Additionally, we suggest programs invest in the long-term participation of individual fishermen, carefully weigh the pros and cons of involvement in regulatory reporting, and plan data products and applications well in advance to ensure that the sampling scheme and granularity of the data meet the needs of stock assessment, ecosystem, and oceanographic scientists.

First report of Brenneria goodwinii causing acute oak decline on Quercus suber in Portugal - C. Fernandes; L. Duarte; P. Naves; E. Sousa; L. Cruz (Journal of Plant Pathology, 2022)

Decontamination of real urban sewage—comparison between Fenton and electrochemical oxidation - Jenivaldo L. de Araújo; Jaceguai S. da Silva; Fábio A. S. Santos; Cenira M. de Carvalho; José Leandro S. Duarte; Josealdo Tonholo; Carmem L. P. S. Zanta (Environmental Science and Pollution Research, 2022)

Exposure to leucine induces oxidative stress in the brain of zebrafish - Bianca Z. de Medeiros; Leticia B. Wessler; Mariane B. Duarte; Isabela S. Lemos; Gabriela Candiotto; Rafael O. Canarim; Paulo C. L. dos Santos; Carolina A. Torres; Giselli Scaini; Eduardo P. Rico; Jaqueline S. Generoso; Emilio L. Streck (Metabolic Brain Disease, 2022)

Trade-offs between succulent and non-succulent epiphytes underlie variation in drought tolerance and avoidance - S. G. Gotsch; C. B. Williams; R. Bicaba; R. Cruz-de Hoyos; A. Darby; K. Davidson; M. Dix; V. Duarte; A. Glunk; L. Green; B. Ferguson; K. Muñoz-Elizondo; et al. (Oecologia, 2022)

Identification of potential new mosquito-associated viruses of adult Aedes aegypti mosquitoes from Tocantins state, Brazil - Matheus A. Duarte; Fabrício S. Campos; Osvaldo F. Araújo Neto; Leonardo A. Silva; Arthur B. Silva; Thalita C. Aguiar; Raissa N. Santos; Ueric J. B. Souza; Giselly B. Alves; Fernando L. Melo; Daniel M. P. Ardisson-Araujo; Raimundo W. S. Aguiar; et al. (Brazilian Journal of Microbiology, 2022)

Projecting coral responses to intensifying marine heatwaves under ocean acidification - Shannon G. Klein; Nathan R. Geraldi; Andrea Anton; Sebastian Schmidt‐Roach; Maren Ziegler; Maha J. Cziesielski; Cecilia Martin; Nils Rädecker; Thomas L. Frölicher; Peter J. Mumby; John M. Pandolfi; David J. Suggett; et al. (Global Change Biology, 2022)
Over this century, coral reefs will run the gauntlet of climate change, as marine heatwaves (MHWs) become more intense and frequent, and ocean acidification (OA) progresses. However, we still lack a quantitative assessment of how, and to what degree, OA will moderate the responses of corals to MHWs as they intensify throughout this century. Here, we first projected future MHW intensities for tropical regions under three future greenhouse gas emissions scenario (representative concentration pathways, RCP2.6, RCP4.5 and RCP8.5) for the near‐term (2021–2040), mid‐century (2041–2060) and late‐century (2081–2100). We then combined these MHW intensity projections with a global data set of 1,788 experiments to assess coral attribute performance and survival under the three emissions scenarios for the near‐term, mid‐century and late‐century in the presence and absence of OA. Although warming and OA had predominately additive impacts on the coral responses, the contribution of OA in affecting most coral attributes was minor relative to the dominant role of intensifying MHWs. However, the addition of OA led to greater decreases in photosynthesis and survival under intermediate and unrestricted emissions scenario for the mid‐ and late‐century than if intensifying MHWs were considered as the only driver. These results show that role of OA in modulating coral responses to intensifying MHWs depended on the focal coral attribute and extremity of the scenario examined. Specifically, intensifying MHWs and OA will cause increasing instances of coral bleaching and substantial declines in coral productivity, calcification and survival within the next two decades under the low and intermediate emissions scenario. These projections suggest that corals must rapidly adapt or acclimatize to projected ocean conditions to persist, which is far more likely under a low emissions scenario and with increasing efforts to manage reefs to enhance resilience.

Variable response of Red Sea coral communities to recent disturbance events along a latitudinal gradient - Nicholas M. Hammerman; Alberto Rodriguez-Ramirez; Timothy L. Staples; Thomas M. DeCarlo; Vincent Saderne; George Roff; Nicole Leonard; Jian-xin Zhao; Susann Rossbach; Michelle N. Havlik; Carlos M. Duarte; John M. Pandolfi (Marine Biology, 2021)

A methanol extract and N,N-dimethyltryptamine from Psychotria viridis Ruiz & Pav. inhibit Zika virus infection in vitro - Thaís F. S. Moraes; Ariane C. Ferraz; Waleska S. da Cruz Nizer; Antônio H. Tótola; Débora B. S. Soares; Lucienir P. Duarte; Sidney A. Vieira-Filho; Cintia L. B. Magalhães; José C. de Magalhães (Archives of Virology, 2021)

Integrating environmental variability to broaden the research on coral responses to future ocean conditions - Maren Ziegler; Andrea Anton; Shannon G. Klein; Nils Rädecker; Nathan R. Geraldi; Sebastian Schmidt‐Roach; Vincent Saderne; Peter J. Mumby; Maha J. Cziesielski; Cecilia Martin; Thomas L. Frölicher; John M. Pandolfi; et al. (Global Change Biology, 2021)
Our understanding of the response of reef‐building corals to changes in their physical environment is largely based on laboratory experiments, analysis of long‐term field data, and model projections. Experimental data provide unique insights into how organisms respond to variation of environmental drivers. However, an assessment of how well experimental conditions cover the breadth of environmental conditions and variability where corals live successfully is missing. Here, we compiled and analyzed a globally distributed dataset of in‐situ seasonal and diurnal variability of key environmental drivers (temperature, p CO 2 , and O 2 ) critical for the growth and livelihood of reef‐building corals. Using a meta‐analysis approach, we compared the variability of environmental conditions assayed in coral experimental studies to current and projected conditions in their natural habitats. We found that annual temperature profiles projected for the end of the 21st century were characterized by distributional shifts in temperatures with warmer winters and longer warm periods in the summer, not just peak temperatures. Furthermore, short‐term hourly fluctuations of temperature and p CO 2 may regularly expose corals to conditions beyond the projected average increases for the end of the 21st century. Coral reef sites varied in the degree of coupling between temperature, p CO 2 , and dissolved O 2 , which warrants site‐specific, differentiated experimental approaches depending on the local hydrography and influence of biological processes on the carbonate system and O 2 availability. Our analysis highlights that a large portion of the natural environmental variability at short and long timescales is underexplored in experimental designs, which may provide a path to extend our understanding on the response of corals to global climate change.

Biodiversity Assessment and Geographical Affinities of Discards in Clam Fisheries in the Atlantic–Mediterranean Transition (Northern Alboran Sea) - J. Urra; P. Marina; A. Rojas García; E. León Duarte; H. Gallardo-Roldán; B. Orue Montaner; M. Lozano; J. M. Serna; A. Garrido; A. J. Ibáñez Yuste; A. Terrón-Sigler; J. Baro; et al. (Thalassas: An International Journal of Marine Sciences, 2021)

Cecropia hololeuca : A new source of compounds with potential anti-inflammatory action - Emanuelle G. Machado; Oswaldo Cardoso; Nerilson M. Lima; Paloma E. Carvalho; Alice D. Barbosa; Guilherme F. S. Sobrinho; Jennifer F. Duarte; Laryssa R. Coelho; Pietra P. C. Soares; Ayane G. Orneles; Ana Carolina B. Santos; Kamila B. Santos; et al. (Natural Product Research, 2021)

First Application of 360-Degree Camera Technology to Marine Predator Bio-Logging - Austin J. Gallagher; Nourah A. Alsudairy; Brendan D. Shea; Nicholas L. Payne; Carlos M. Duarte (Frontiers in Marine Science, 2021)
Animal-borne video camera systems have long-been used to capture the fine-scale behaviors and unknown aspects of the biology of marine animals. However, their utility to serve as robust scientific tools in the greater bio-logging research community has not been fully realized. Here we provide, for the first time, an application of 360-degree camera technology to a marine organism, using a large tiger shark as a proof-of-concept case study. Leveraging the three-dimensional nature of the imaging technology, we derived 224 seafloor habitat assessments over the course of the nearly 1-h track, whereby the shark was able to survey ∼23,000 square meters of seafloor; over three-times greater than the capacity of non 360-degree cameras. The resulting data provided detailed information on habitat use, diving behavior, and swimming speed, as well seafloor mapping. Our results suggest that 360-degree cameras provide complimentary benefits—and in some cases superior efficiency—than unidirectional video packages, with an enhanced capacity to map seafloor.

Numerical Prediction of the Boundary-Layer Flow Over the Bolund Hill: Assessment of Turbulence Models and Advection Schemes - A. M. G. Lopes; N. G. L. Duarte; O. H. Sánchez; R. Daus; H. Koch (Boundary-Layer Meteorology, 2021)

Exposure to pH 3.5 water has no effect on the gills of the Amazonian tambaqui (Colossoma macropomum) - R. J. Gonzalez; M. L. Patrick; R. M. Duarte; A. Casciato; J. Thackeray; N. Day; A. L. Val (Journal of Comparative Physiology B, 2021)

Whole body vibration influence on bus fare collectors evaluated by using a brain training mobile app - S. G. Firmino; M. L. M. Duarte; J. A. B. Neves; P. A. X. Viana; F. S. B. de Araújo (International Archives of Occupational and Environmental Health, 2021)

Cadaverine and Spermine Elicit Ca2+ Uptake in Human CP Cells via a Trace Amine-Associated Receptor 1 Dependent Pathway - D. Almeida-Santos; A. C. Duarte; I. Gonçalves; Catarina L. Ferreira; I. Ferrer; Hiroshi Ishikawa; Christian Schwerk; Horst Schroten; Cecília R. A. Santos (Journal of Molecular Neuroscience, 2021)

Impact of a tarsonemid prey mite and its fungal diet on the reproductive performance of a predatory mite - Dominiek Vangansbeke; Marcus V. A. Duarte; Jonas Merckx; Alfredo Benavente; Wojciech L. Magowski; Soraya C. França; Karel Bolckmans; Felix L. Wäckers (Experimental and Applied Acarology, 2021)

Susan Lynn Williams: the Life of an Exceptional Scholar, Leader, and Friend (1951–2018) - William C. Dennison; Matthew E. S. Bracken; Maria Brown; John F. Bruno; James T. Carlton; Robert C. Carpenter; Tim J. B. Carruthers; Megan N. Dethier; Carlos M. Duarte; Thomas R. Fisher; James W. Fourqurean; Richard K. Grosberg; et al. (Estuaries and Coasts, 2021)
Susan Lynn Williams (1951–2018) was an exceptional marine ecologist whose research focused broadly on the ecology of benthic nearshore environments dominated by seagrasses, seaweeds, and coral reefs. She took an empirical approach founded in techniques of physiological ecology. Susan was committed to applying her research results to ocean management through outreach to decision-makers and resource managers. Susan’s career included research throughout the USA in tropical, temperate, and polar regions, but she specialized in tropical marine ecology. Susan’s scholarship, leadership, and friendship touched many people, leading to this multi-authored paper. Susan’s scholarship was multi-faceted, and she excelled in scientific discovery, integration of scientific results, application of science for conservation, and teaching, especially as a mentor to undergraduate and graduate students and postdoctoral scholars. Susan served in a variety of leadership positions throughout her career. She embodied all facets of leadership; leading by example, listening to others, committing to the “long haul,” maintaining trust, and creating a platform for all to shine. Susan was an important role model for women in science. Susan was also a loyal friend, maintaining friendships for many decades. Susan loved cooking and entertaining with friends. This paper provides an overview of the accomplishments of Susan in the broad categories of scholarship, leadership, and friendship.

Administration of branched-chain amino acids alters epigenetic regulatory enzymes in an animal model of Maple Syrup Urine Disease - Emilio L. Streck; Felipe P. Bussular; Leticia B. Wessler; Mariane B. Duarte; Victoria L. Rezende; Matheus S. Rodrigues; Carolina A. Torres; Isabela S. Lemos; Gabriela Candiotto; Fernanda F. Gava; Jade de Oliveira; Samira S. Valvassori (Metabolic Brain Disease, 2021)

Reduced cutaneous inflammation associated with antioxidant action after topical application of the aqueous extract of Annona muricata leaves - Luana M. Cercato; Jéssica M. D. Araújo; Alan S. Oliveira; Allan J. O. Melo; Bruno S. Lima; Edmilson W. P. dos Santos; Agenor G. dos S. Neto; Ricardo L. C. de Albuquerque-Júnior; Marcelo C. Duarte; Adriano A. S. Araujo; Ana Mara O. Silva; Renata Grespan; et al. (Inflammopharmacology, 2021)

The metabolic effect of α-ketoisocaproic acid: in vivo and in vitro studies - Hémelin R. Farias; Joice R. Gabriel; Maria Laura Cecconi; Isabela S. Lemos; Victoria L. de Rezende¹; Letícia B. Wessler; Mariane B. Duarte; Giselli Scaini; Jade de Oliveira; Emilio L. Streck (Metabolic Brain Disease, 2021)

Effects of thermal shock on the survival and reproduction of Stratiolaelaps scimitus (Mesostigmata: Laelapidae) - Priscilla C. Gobbi; Juliano L. P. Duarte; Lucas R. da Silva; Dori E. Nava; Gustavo Sessa Fialho; Uemerson S. da Cunha; Adriane da F. Duarte (Experimental and Applied Acarology, 2020)

Insect chemical ecology: chemically mediated interactions and novel applications in agriculture - Crispus M. Mbaluto; Pascal M. Ayelo; Alexandra G. Duffy; Anna L. Erdei; Anaїs K. Tallon; Siyang Xia; Gabriela Caballero-Vidal; Urban Spitaler; Magdolna O. Szelényi; Gonçalo A. Duarte; William B. Walker; Paul G. Becher (Arthropod-Plant Interactions, 2020)
Insect chemical ecology (ICE) evolved as a discipline concerned with plant–insect interactions, and also with a strong focus on intraspecific pheromone-mediated communication. Progress in this field has rendered a more complete picture of how insects exploit chemical information in their surroundings in order to survive and navigate their world successfully. Simultaneously, this progress has prompted new research questions about the evolution of insect chemosensation and related ecological adaptations, molecular mechanisms that mediate commonly observed behaviors, and the consequences of chemically mediated interactions in different ecosystems. Themed meetings, workshops, and summer schools are ideal platforms for discussing scientific advancements as well as identifying gaps and challenges within the discipline. From the 11th to the 22nd of June 2018, the 11th annual PhD course in ICE was held at the Swedish University of Agricultural Sciences (SLU) Alnarp, Sweden. The course was made up of 35 student participants from 22 nationalities (Fig. 1a) as well as 32 lecturers. Lectures and laboratory demonstrations were supported by literature seminars, and four broad research areas were covered: (1) multitrophic interactions and plant defenses, (2) chemical communication focusing on odor sensing, processing, and behavior, (3) disease vectors, and (4) applied aspects of basic ICE research in agriculture. This particular article contains a summary and brief synthesis of these main emergent themes and discussions from the ICE 2018 course. In addition, we also provide suggestions on teaching the next generation of ICE scientists, especially during unprecedented global situations.

Milk yield and composition and body weight of offsprings of mixed-breed goats on semi-arid rangelands with different rainfall - M. J. Flores-Najera; L. I. Vélez-Monroy; J. I. Sánchez-Duarte; V. Cuevas-Reyes; M. Mellado; C. A. Rosales-Nieto (Tropical Animal Health and Production, 2020)

Costus stripe mosaic virus, a tentative new member of the genus Potyvirus - M. Amelia V. Alexandre; Ligia M. L. Duarte; Pedro L. Ramos-González; Alexandre L. R. Chaves; Ricardo Harakava; Leilane K. Rodrigues; Camila Chabi-Jesus; E. W. Kitajima (Archives of Virology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

A process‐based metacommunity framework linking local and regional scale community ecology - Patrick L. Thompson; Laura Melissa Guzman; Luc De Meester; Zsófia Horváth; Robert Ptacnik; Bram Vanschoenwinkel; Duarte S. Viana; Jonathan M. Chase (Ecology Letters, 2020)
The metacommunity concept has the potential to integrate local and regional dynamics within a general community ecology framework. To this end, the concept must move beyond the discrete archetypes that have largely defined it (e.g. neutral vs. species sorting) and better incorporate local scale species interactions and coexistence mechanisms. Here, we present a fundamental reconception of the framework that explicitly links local coexistence theory to the spatial processes inherent to metacommunity theory, allowing for a continuous range of competitive community dynamics. These dynamics emerge from the three underlying processes that shape ecological communities: (1) density‐independent responses to abiotic conditions, (2) density‐dependent biotic interactions and (3) dispersal. Stochasticity is incorporated in the demographic realisation of each of these processes. We formalise this framework using a simulation model that explores a wide range of competitive metacommunity dynamics by varying the strength of the underlying processes. Using this model and framework, we show how existing theories, including the traditional metacommunity archetypes, are linked by this common set of processes. We then use the model to generate new hypotheses about how the three processes combine to interactively shape diversity, functioning and stability within metacommunities.

Nicorandil Affects Mitochondrial Respiratory Chain Function by Increasing Complex III Activity and ROS Production in Skeletal Muscle Mitochondria - E. Sánchez-Duarte; C. Cortés-Rojo; L. A. Sánchez-Briones; J. Campos-García; A. Saavedra-Molina; I. Delgado-Enciso; U. A. López-Lemus; R. Montoya-Pérez (The Journal of Membrane Biology, 2020)

Melatonin ameliorates oxidative stress and DNA damage of rats subjected to a chemically induced chronic model of Maple Syrup Urine Disease - Leticia B. Wessler; Kely Ise; Isabela C. Lemos; Victoria L. Rezende; Mariane B. Duarte; Adriani P. Damiani; Jade de Oliveira; Vanessa M. de Andrade; Emilio L. Streck (Metabolic Brain Disease, 2020)

Incorporating the sampling effectiveness of detection dogs in the faecal standing crop method - Amanda R. Da Silva; Márcio L. De Oliveira; José M. B. Duarte (European Journal of Wildlife Research, 2020)

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Differential thermal tolerance between algae and corals may trigger the proliferation of algae in coral reefs - Andrea Anton; Janna L. Randle; Francisca C. Garcia; Susann Rossbach; Joanne I. Ellis; Michael Weinzierl; Carlos M. Duarte (Global Change Biology, 2020)
Marine heatwaves can lead to rapid changes in entire communities, including in the case of shallow coral reefs the potential overgrowth of algae. Here we tested experimentally the differential thermal tolerance between algae and coral species from the Red Sea through the measurement of thermal performance curves and the assessment of thermal limits. Differences across functional groups (algae vs. corals) were apparent for two key thermal performance metrics. First, two reef‐associated algae species ( Halimeda tuna and Turbinaria ornata ) had higher lethal thermal limits than two coral species ( Pocillopora verrucosa and Stylophora pistillata ) conferring those species of algae with a clear advantage during heatwaves by surpassing the thermal threshold of coral survival. Second, the coral species had generally greater deactivation energies for net and gross primary production rates compared to the algae species, indicating greater thermal sensitivity in corals once the optimum temperature is exceeded. Our field surveys in the Red Sea reefs before and after the marine heatwave of 2015 show a change in benthic cover mainly in the southern reefs, where there was a decrease in coral cover and a concomitant increase in algae abundance, mainly turf algae. Our laboratory and field observations indicate that a proliferation of algae might be expected on Red Sea coral reefs with future ocean warming.

Caffeine removal using Elaeis guineensis activated carbon: adsorption and RSM studies - Larissa L. A. Melo; Alessandra H. Ide; José Leandro S. Duarte; Carmem Lucia P. S. Zanta; Leonardo M. T. M. Oliveira; Wagner R. O. Pimentel; Lucas Meili (Environmental Science and Pollution Research, 2020)

The big picture of field hydrology studies in Brazil - Davi C. D. Melo; Jamil A. A. Anache; Cristiano das N. Almeida; Jaqueline V. Coutinho; Geraldo M. Ramos Filho; Lívia M. P. Rosalem; Natália S. Pelinson; Guilherme L. R. A. Ferreira; Dimaghi Schwamback; Kalyl G. Calixto; João P. G. Siqueira; Jean C. Duarte-Carvajalino; et al. (Hydrological Sciences Journal, 2020)

Toxicities of acetogenin-based bioacaricides against two-spotted spider mite and selectivity to its phytoseiid predators - J. Miotto; A. F. Duarte; D. Bernardi; L. P. Ribeiro; F. Andreazza; U. S. Cunha (Experimental and Applied Acarology, 2020)

Non-Cytotoxic Sulfated Heterorhamnan from Gayralia brasiliensis Green Seaweed Reduces Driver Features of Melanoma Metastatic Progression - D. L. Bellan; E. Mazepa; S. M. P. Biscaia; J. P. Gonçalves; C. C. Oliveira; G. R. Rossi; L. G. Ferreira; M. D. Noseda; E. S. Trindade; M. E. R. Duarte; C. R. C. Franco (Marine Biotechnology, 2020)

Heat Waves Are a Major Threat to Turbid Coral Reefs in Brazil - Gustavo A. S. Duarte; Helena D. M. Villela; Matheus Deocleciano; Denise Silva; Adam Barno; Pedro M. Cardoso; Caren L. S. Vilela; Phillipe Rosado; Camila S. M. A. Messias; Maria Alejandra Chacon; Erika P. Santoro; Daniele B. Olmedo; et al. (Frontiers in Marine Science, 2020)

Estimates of environmental loading from copper alloy materials - Patrick J. Earley; Brandon L. Swope; Marienne A. Colvin; Gunther Rosen; Pei-Fang Wang; Jessica Carilli; Ignacio Rivera-Duarte (Biofouling, 2020)

Removal of Reactive Dyes from Aqueous Solution by Fenton Reaction: Kinetic Study and Phytotoxicity Tests - Marcela G. R. Tavares; Danilo H. S. Santos; Mariana G. Tavares; José L. S. Duarte; Lucas Meili; Wagner R. O. Pimentel; Josealdo Tonholo; Carmem L. P. S. Zanta (Water, Air, & Soil Pollution, 2020)

Comparing Electrochemical and Fenton-Based Processes for Aquaculture Biocide Degradation - Jéssica M. O. Melo; José L. S. Duarte; Alice B. Ferro; Lucas Meili; Carmen L. P. S. Zanta (Water, Air, & Soil Pollution, 2020)

The role of shrimp micro RNA s in immune response and beyond - Ramiro J. González‐Duarte; Fernando L. García‐Carreño (Reviews in Aquaculture, 2020)
Micro RNA s are a class of small non‐coding RNA s that regulate gene expression at post‐transcriptional level. Regulatory RNA s were discovered in the nematode Caenorhabditis elegans , since then, their biological functions have been studied on different animals, including marine organisms. Several species of penaeid shrimp are important in ecology and fishing, including aquaculture. Overcrowding in aquaculture calls for infectious diseases, which threaten the development of shrimp aquaculture worldwide. Given that micro RNA s play crucial regulatory roles in a wide variety of biological processes, there is a scientific interest to understand their contribution on shrimp physiology and pathology, specifically during immune and stress response. Increasing evidence has shown that the expression of micro RNA s is affected during virus or bacterial infection and upon stress in shrimp. This information provides valuable insights for a better understanding of shrimp biology by means of micro RNA regulation to bacterial and viral diseases.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Peeling the Otolith of Fish: Optimal Parameterization for Micro-CT Scanning - Jonas E. Vasconcelos-Filho; Felix S. L. Thomsen; Borko Stosic; Antonio C. D. Antonino; Daniel A. Duarte; Richard J. Heck; Rosangela P. T. Lessa; Francisco M. Santana; Beatrice P. Ferreira; Paulo J. Duarte-Neto (Frontiers in Marine Science, 2019)

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Tactile Stimulation on Adulthood Modifies the HPA Axis, Neurotrophic Factors, and GFAP Signaling Reverting Depression-Like Behavior in Female Rats - Kr. Roversi; Caren Tatiane de David Antoniazzi; L. H. Milanesi; H. Z. Rosa; M. Kronbauer; D. R. Rossato; T. Duarte; M. M. Duarte; Marilise E. Burger (Molecular Neurobiology, 2019)

Tomato mottle mosaic virus in Brazil and its relationship with Tm-22 gene - Alice Nagai; Lígia M. L. Duarte; Alexandre L. R. Chaves; Lázaro E. P. Peres; Déborah Y. A. C. dos Santos (European Journal of Plant Pathology, 2019)

Global challenges for seagrass conservation - Richard K. F. Unsworth; Len J. McKenzie; Catherine J. Collier; Leanne C. Cullen-Unsworth; Carlos M. Duarte; Johan S. Eklöf; Jessie C. Jarvis; Benjamin L. Jones; Lina M. Nordlund (Ambio, 2019)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Deep Penetration of Kelps Offshore Along the West Coast of Greenland - Dorte Krause-Jensen; Mikael K. Sejr; Annette Bruhn; Michael B. Rasmussen; Peter Bondo Christensen; Jørgen L. S. Hansen; Carlos M. Duarte; Grethe Bruntse; Susse Wegeberg (Frontiers in Marine Science, 2019)

Involvement of the Cholinergic Parameters and Glial Cells in Learning Delay Induced by Glutaric Acid: Protection by N-Acetylcysteine - Fernanda Silva Rodrigues; Viviane Nogueira de Zorzi; Marla Parizzi Funghetto; Fernanda Haupental; Alexandra Seide Cardoso; Sara Marchesan; Andréia M. Cardoso; Maria Rosa C. Schinger; Alencar Kolinski Machado; Ivana Beatrice Mânica da Cruz; Marta Maria Medeiros Frescura Duarte; Léder L. Xavier; et al. (Molecular Neurobiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Evaluation of the effects of extracts of Maytenus imbricata (Celastraceae) on the treatment of inflammatory and metabolic dysfunction induced by high-refined carbohydrate diet - C. C. Veloso; M. C. Oliveira; V. G. Rodrigues; C. C. Oliveira; L. P. Duarte; M. M. Teixeira; A. V. M. Ferreira; A. C. Perez (Inflammopharmacology, 2019)

Fingerprinting Blue Carbon: Rationale and Tools to Determine the Source of Organic Carbon in Marine Depositional Environments - Nathan R. Geraldi; Alejandra Ortega; Oscar Serrano; Peter I. Macreadie; Catherine E. Lovelock; Dorte Krause-Jensen; Hilary Kennedy; Paul S. Lavery; Michael L. Pace; Joeri Kaal; Carlos M. Duarte (Frontiers in Marine Science, 2019)

Citalopram Reduces Aggregation of ATXN3 in a YAC Transgenic Mouse Model of Machado-Joseph Disease - Naila S. Ashraf; Sara Duarte-Silva; Emily D. Shaw; Patrícia Maciel; Henry L. Paulson; Andreia Teixeira-Castro; Maria do Carmo Costa (Molecular Neurobiology, 2019)

P2X7 Receptors Mediate CO-Induced Alterations in Gene Expression in Cultured Cortical Astrocytes—Transcriptomic Study - Sara R. Oliveira; Cláudia Figueiredo-Pereira; Carlos B. Duarte; Helena L. A. Vieira (Molecular Neurobiology, 2019)

Does dissolved organic carbon from Amazon black water (Brazil) help a native species, the tambaqui Colossoma macropomum to maintain ionic homeostasis in acidic water? - Helen Sadauskas‐Henrique; Chris M. Wood; Luciana R. Souza‐Bastos; Rafael M. Duarte; Donald S. Smith; Adalberto L. Val (Journal of Fish Biology, 2019)
To assess how the quality and properties of the natural dissolved organic carbon (DOC) could drive different effects on gill physiology, we analysed the ionoregulatory responses of a native Amazonian fish species, the tambaqui Colossoma macropomum , to the presence of dissolved organic carbon (DOC; 10 mg l −1 ) at both pH 7.0 and pH 4.0 in ion‐poor water. The DOC was isolated from black water from São Gabriel da Cachoeira (SGC) in the upper Rio Negro of the Amazon (Brazil) that earlier been shown to protect a non‐native species, zebrafish Danio rerio against low pH under similar conditions. Transepithelial potential (TEP), net flux rates of Na + , Cl − and ammonia and their concentrations in plasma and Na + , K + ATPase; v‐type H + ATPase and carbonic anhydrase activities in gills were measured. The presence of DOC had negligible effects at pH 7.0 apart from lowering the TEP, but it prevented the depolarization of TEP that occurred at pH 4.0 in the absence of DOC. However, contrary to our initial hypothesis, SGC DOC was not protective against the effects of low pH. Colossoma macropomum exposed to SGC DOC at pH 4.0 experienced greater net Na + and Cl − losses, decreases of Na + and Cl − concentrations in plasma and elevated plasma ammonia levels and excretion rates, relative to those exposed in the absence of DOC. Species‐specific differences and changes in DOC properties during storage are discussed as possible factors influencing the effectiveness of SGC DOC in ameliorating the effects of the acid exposure.

Spatial Variation in Mercury Bioaccumulation and Magnification in a Temperate Estuarine Food Web - Vanessa F. Fonseca; Susana França; Bernardo Duarte; Isabel Caçador; Henrique N. Cabral; Cláudia L Mieiro; João P. Coelho; Eduarda Pereira; Patrick Reis-Santos (Frontiers in Marine Science, 2019)

Better estimates of soil carbon from geographical data: a revised global approach - Sandra Duarte-Guardia; Pablo L. Peri; Wulf Amelung; Douglas Sheil; Shawn W. Laffan; Nils Borchard; Michael I. Bird; Wouter Dieleman; David A. Pepper; Brian Zutta; Esteban Jobbagy; Lucas C. R. Silva; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

Effects of hydroelectric turbine noise on the behaviour of Leporinus taeniatus (Characiformes: Anostomidae) in captivity - Marina H. L. Duarte; Rafael M. C. Melo; Marina D. A. Scarpelli; Thiago M. A. Carvalho; Linilson R. Padovese; Nilo Bazzoli; Elizete Rizzo (Journal of Ethology, 2019)

Ocean Solutions to Address Climate Change and Its Effects on Marine Ecosystems - Jean-Pierre Gattuso; Alexandre K. Magnan; Laurent Bopp; William W. L. Cheung; Carlos M. Duarte; Jochen Hinkel; Elizabeth Mcleod; Fiorenza Micheli; Andreas Oschlies; Phillip Williamson; Raphaël Billé; Vasiliki I. Chalastani; et al. (Frontiers in Marine Science, 2018)

Physiological protective action of dissolved organic carbon on ion regulation and nitrogenous waste excretion of zebrafish (Danio rerio) exposed to low pH in ion-poor water - Rafael M. Duarte; Chris M. Wood; Adalberto L. Val; D. Scott Smith (Journal of Comparative Physiology B, 2018)

Efficacy of plants extracts from the Cerrado against adult female of Dermacentor nitens (Acari: Ixodidae) - V. O. Vasconcelos; E. G. L. Costa; V. R. Moreira; F. Morais-Costa; E. R. Duarte (Experimental and Applied Acarology, 2018)

Creation of a coastal evolution prognostic model using shoreline historical data and techniques of digital image processing in a GIS environment for generating future scenarios - Willamys R. N. de Sousa; Michael V. S. Souto; Stefanny S. Matos; Cynthia R. Duarte; Ana R. G. N. L. Salgueiro; Cláudio A. da Silva Neto (International Journal of Remote Sensing, 2018)

Aged rats are more vulnerable than adolescents to “ecstasy”-induced toxicity - R. Feio-Azevedo; V. M. Costa; D. J. Barbosa; A. Teixeira-Gomes; I. Pita; S. Gomes; F. C. Pereira; M. Duarte-Araújo; J. A. Duarte; F. Marques; E. Fernandes; M. L. Bastos; et al. (Archives of Toxicology, 2018)

Effects of a nanoemulsion with Copaifera officinalis oleoresin against monogenean parasites of Colossoma macropomum: A Neotropical Serrasalmidae - D S S Valentim; J L Duarte; A E M F M Oliveira; R A S Cruz; J C T Carvalho; C Solans; C P Fernandes; M Tavares‐Dias (Journal of Fish Diseases, 2018)
Monogeneans are ectoparasites that may cause losses in production and productivity in the aquaculture of Colossoma macropomum . Chemotherapeutics used in aquaculture usually have major adverse effects on fish; hence, the use of essential oils has been considered advantageous, but these are not soluble in water. Thus, the use of nanostructures to enhance water solubility of compounds and improve bioactivity may be very promising. This study investigated the antiparasitic activity of nanoemulsion prepared with Copaifera officinalis oleoresin (50, 100, 150, 200 and 300 mg/L), against monogenean parasites from the gills of C. macropomum . The particle size distribution and zeta potential suggested that a potentially kinetic stable system was generated. The nanoemulsion from C. officinalis oleoresin achieved high efficacy (100%) at low concentrations (200 and 300 mg/L) after 15 min of exposure. This was the first time that a nanoemulsion was generated from C. officinalis oleoresin using a solvent‐free, non‐heating and low‐energy method. Moreover, this was the first time that an antiparasitic against monogeneans on fish gills, based on nanoemulsion of C. officinalis oleoresin, was tested.

High waterborne Mg does not attenuate the toxic effects of Fe, Mn, and Ba on Na+ regulation of Amazonian armored catfish tamoatá (Hoplosternum litoralle) - Rafael M. Duarte; Ana Paula Benaduce; Luciano Garcia; Levy C. Gomes; Adriana Chippari Gomes; Adalberto L. Val; Bernardo Baldisserotto (Environmental Science and Pollution Research, 2018)

Detection of the antiviral activity of epicatechin isolated from Salacia crassifolia (Celastraceae) against Mayaro virus based on protein C homology modelling and virtual screening - P. G. Ferreira; A. C. Ferraz; J. E. Figueiredo; C. F. Lima; V. G. Rodrigues; A. G. Taranto; J. M. S. Ferreira; G. C. Brandão; S. A. Vieira-Filho; L. P. Duarte; C. L. de Brito Magalhães; J. C. de Magalhães (Archives of Virology, 2018)

β-(1→6)-d-glucan secreted during the optimised production of exopolysaccharides by Paecilomyces variotii has immunostimulatory activity - Erica F. Osaku; Rafael A. Menolli; Claudia R. L. de M. Costa; Fernando Henrique G. Tessaro; Renan H. de Melo; Alex E. do Amaral; Péricles A. D. Duarte; Arquimedes Paixão de Santana Filho; Andrea Caroline Ruthes; José Luis da C. Silva; Rosiane G. Mello (Antonie van Leeuwenhoek, 2018)

Cookie‐cutter shark Isistius spp. predation upon different tuna species from the south‐western Atlantic Ocean - Y. V. Niella; L. A. G. Duarte; V. R. Bandeira; O. Crespo; D. Beare; F. H. V. Hazin (Journal of Fish Biology, 2018)
The predation of cookie‐cutter sharks Isistius spp. upon the early life stages of yellowfin tuna Thunnus albacares , skipjack tuna Katsuwonus pelamis and little tunny Euthynnus alletteratus are described. New evidence suggesting a connection between commercial fishing and predation by Isistius sp. is presented, with these sharks biting tunas hooked in surface waters during daylight. The healing patterns of the wounds made by the sharks are described in detail and, although such damage is known to negatively influence market price elsewhere, it is not the case on the south‐east Brazilian coast.

Nanoemulsion from essential oil of Pterodon emarginatus (Fabaceae) shows in vitro efficacy against monogeneans of Colossoma macropomum (Pisces: Serrasalmidae) - D S S Valentim; J L Duarte; A E M F M Oliveira; R A S Cruz; J C T Carvalho; E C Conceição; C P Fernandes; M Tavares‐Dias (Journal of Fish Diseases, 2018)
Outbreaks of diseases pose a major threat to sustainable aquaculture development worldwide. Application of herbal products to combat parasitic diseases provides an alternative approach for sustainable aquaculture. This study investigated the in vitro antiparasitic effects of an oil‐in‐water nanoemulsion prepared using the essential oil from Pterodon emarginatus , against monogeneans infesting Colossoma macropomum . Gill arches from C. macropomum (47.6 ± 14.5 g and 13.5 ± 1.4 cm) that were naturally parasitized by Anacanthorus spathulatus , Notozothecium janauachensis and Mymarothecium boegeri were immersed in different dispersions of the P. emarginatus nanoemulsions (0, 50, 100, 200, 400 and 600 mg/L). The major compounds presented in the essential oil of P. emarginatus were β‐elemene, β‐caryophyllene and α‐humulene. Characterization of these nanoemulsions showed that they have a small mean droplet size and low polydispersity index, which is concordant with stable systems. In this in vitro trial, the P. emarginatus nanoemulsion concentrations of 100, 200, 400 and 600 mg/L presented 100% helminthic efficacy against monogeneans of the gills of C. macropomum . The highest two concentrations used (400 and 600 mg/L) were seen to immobilize the parasites after only 15 min. Therefore, it would be worthwhile testing these concentrations in therapeutic baths against monogeneans of C. macropomum .

Tingenone, a pentacyclic triterpene, induces peripheral antinociception due to cannabinoid receptors activation in mice - C. C. Veloso; R. C. M. Ferreira; V. G. Rodrigues; L. P. Duarte; A. Klein; I. D. Duarte; T. R. L. Romero; A. C. Perez (Inflammopharmacology, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Mining noise affects loud call structures and emission patterns of wild black-fronted titi monkeys - M. H. L. Duarte; M. C. Kaizer; R. J. Young; M. Rodrigues; R. S. Sousa-Lima (Primates, 2018)

Comparing Contact Calling Between Black Tufted-Ear Marmosets (Callithrix penicillata) in a Noisy Urban Environment and in a Quiet Forest - S. G. Santos; M. H. L. Duarte; R. S. Sousa-Lima; R. J. Young (International Journal of Primatology, 2017)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Experimental and theoretical studies of emodin interacting with a lipid bilayer of DMPC - Antonio R. da Cunha; Evandro L. Duarte; Hubert Stassen; M. Teresa Lamy; Kaline Coutinho (Biophysical Reviews, 2017)

Structural insights on biologically relevant cationic membranes by ESR spectroscopy - Julio H. K. Rozenfeld; Evandro L. Duarte; Tiago R. Oliveira; M. Teresa Lamy (Biophysical Reviews, 2017)

Cognitive Event-Related Potentials (P300) and Cognitive Impairment in Duchenne Muscular Dystrophy - N. Esquitin-Garduño; R. E. Escobar-Cedillo; B. G. Flores-Avalos; G. Escobar-Cedillo; A. Miranda-Duarte; L. B. López-Hernández; V. I. Orellana-Villazón; R. M. Coral-Vázquez; S. García; B. Gómez-Díaz (Neurophysiology, 2017)

Production of Electrospun Fast-Dissolving Drug Delivery Systems with Therapeutic Eutectic Systems Encapsulated in Gelatin - Francisca Mano; Marta Martins; Isabel Sá-Nogueira; Susana Barreiros; João Paulo Borges; Rui L. Reis; Ana Rita C. Duarte; Alexandre Paiva (AAPS PharmSciTech, 2017)

Functional soil metagenomics: elucidation of polycyclic aromatic hydrocarbon degradation potential following 12 years of in situ bioremediation - Márcia Duarte; Agnes Nielsen; Amélia Camarinha‐Silva; Ramiro Vilchez‐Vargas; Thomas Bruls; Melissa L. Wos‐Oxley; Ruy Jauregui; Dietmar H. Pieper (Environmental Microbiology, 2017)
Summary A culture‐independent function‐based screening approach was used to assess the microbial aerobic catabolome for polycyclic aromatic hydrocarbons degradation of a soil subjected to 12 years of in situ bioremediation. A total of 422 750 fosmid clones were screened for key aromatic ring‐cleavage activities using 2,3‐dihydroxybiphenyl as substrate. Most of the genes encoding ring‐cleavage enzymes on the 768 retrieved positive fosmids could not be identified using primer‐based approaches and, thus, 205 fosmid inserts were sequenced. Nearly two hundred extradiol dioxygenase encoding genes of three different superfamilies could be identified. Additional key genes of aromatic metabolic pathways were identified, including a high abundance of Rieske non‐heme iron oxygenases that provided detailed information on enzymes activating aromatic compounds and enzymes involved in activation of the side chain of methylsubstituted aromatics. The gained insights indicated a complex microbial network acting at the site under study, which comprises organisms similar to recently identified Immundisolibacter cernigliae TR3.2 and Rugosibacter aromaticivorans Ca6 and underlined the great potential of an approach that combines an activity‐screening, a cost‐effective high‐throughput sequencing of fosmid clones and a phylogenomic‐routed and manually curated database to carefully identify key proteins dedicated to aerobic degradation of aromatic compounds.

Anthocyanins control neuroinflammation and consequent memory dysfunction in mice exposed to lipopolysaccharide - Fabiano B. Carvalho; Jessié M. Gutierres; Andressa Bueno; Paula Agostinho; Adriana M. Zago; Juliano Vieira; Pâmela Frühauf; José L. Cechella; Cristina Wayne Nogueira; Sara M. Oliveira; Caroline Rizzi; Roselia M. Spanevello; et al. (Molecular Neurobiology, 2017)

Guanosine Exerts Neuroprotective Effect in an Experimental Model of Acute Ammonia Intoxication - G. F. Cittolin-Santos; A. M. de Assis; P. A. Guazzelli; L. G. Paniz; J. S. da Silva; M. E. Calcagnotto; G. Hansel; K. C. Zenki; E. Kalinine; M. M. Duarte; D. O. Souza (Molecular Neurobiology, 2017)

Bimodal fire regimes unveil a global‐scale anthropogenic fingerprint - Akli Benali; Bernardo Mota; Nuno Carvalhais; Duarte Oom; Lee M. Miller; Manuel L. Campagnolo; José M. C. Pereira (Global Ecology and Biogeography, 2017)
Aim While fire is recognized as an integral part of the Earth system, the ability of humans to shape fire regimes both spatially and temporally remains poorly understood. Our goals were to identify the extent of fire regimes exhibiting two annual fire seasons and to investigate the environmental correlates of such regimes at the global scale. Location All areas of the globe exhibiting relevant fire activity, at 0.5º spatial resolution. Time period 2002‐2012. Major taxa studied (not applicable). Methods The modality of fire seasonality at the global scale was classified using a 10‐year record of satellite‐derived fire activity and model fitting of circular statistical distributions. The main environmental correlates controlling global fire regimes were then analysed over bimodal and unimodal areas using the Kolmogorov–Smirnov test. Results About 25% of the global land surface with relevant fire activity has two significantly distinct fire seasons per year, with at least one of these seasons occurring under sub‐optimal fire weather conditions. In these bimodal areas, population density and the fraction of fires occurring in actively managed land, especially in croplands and pastures, are significantly higher than in neighbouring unimodal areas. Results reveal that through these land‐use and management practices humans have a strong influence on global patterns of fire seasonality. Main conclusions We identified a bimodal seasonality pattern, previously unreported at the global scale, and show that it reveals an anthropogenic fingerprint on fire regimes. Insights into where and when fire is actively employed as a land management tool enhance our understanding of the role of fire in the Earth system, and highlight the need to better understand how fire practices may change in the future.

The defensive behavioral patterns of captive white-lipped and collared peccary (Mammalia, Tayassuidae): an approach for conservation of the species - Selene S. C. Nogueira; Aline M Reis; Stefane G. Marsaro; José M. B. Duarte; Viviana Moreto; Stella G. C. Lima; Thaise S. O. Costa; Sérgio L G Nogueira-Filho (acta ethologica, 2017)

Open-source GIS application for UAV photogrammetry based on MicMac - L. Duarte; A.C. Teodoro; O. Moutinho; J.A. Gonçalves (International Journal of Remote Sensing, 2017)

Scenario-based analysis of traffic-related PM2.5 concentration: Lisbon case study - Marta V. Faria; Gonçalo O. Duarte; Patrícia C. Baptista; Tiago L. Farias (Environmental Science and Pollution Research, 2017)

Influence of the water-soluble fraction of petroleum on photosynthesis and chemical defenses in two sympatric seaweeds - Angélica R. Soares; Daniel L. R. Simas; Lísia M. Gestinari; Carlos R. Kaiser; Heitor M. Duarte (Journal of Applied Phycology, 2017)

Entangled fates of holobiont genomes during invasion: nested bacterial and host diversities in Caulerpa taxifolia - S. Arnaud‐Haond; T. Aires; R. Candeias; S. J. L. Teixeira; C. M. Duarte; M. Valero; E. A. Serrão (Molecular Ecology, 2017)
Successful prevention and mitigation of biological invasions requires retracing the initial steps of introduction, as well as understanding key elements enhancing the adaptability of invasive species. We studied the genetic diversity of the green alga Caulerpa taxifolia and its associated bacterial communities in several areas around the world. The striking congruence of α and β diversity of the algal genome and endophytic communities reveals a tight association, supporting the holobiont concept as best describing the unit of spreading and invasion. Both genomic compartments support the hypotheses of a unique accidental introduction in the Mediterranean and of multiple invasion events in southern Australia. In addition to helping with tracing the origin of invasion, bacterial communities exhibit metabolic functions that can potentially enhance adaptability and competitiveness of the consortium they form with their host. We thus hypothesize that low genetic diversities of both host and symbiont communities may contribute to the recent regression in the Mediterranean, in contrast with the persistence of highly diverse assemblages in southern Australia. This study supports the importance of scaling up from the host to the holobiont for a comprehensive understanding of invasions.

Erratum to: Physiological differences and changes in global DNA methylation levels in Agave angustifolia Haw. albino variant somaclones during the micropropagation process - Fátima Duarte-Aké; Eduardo Castillo-Castro; Felipe Barredo Pool; Francisco Espadas; Jorge M. Santamaría; Manuel L. Robert; Clelia De-la-Peña (Plant Cell Reports, 2017)

Biological and molecular characterization of a putative new potexvirus infecting Senna occidentalis - Jorge A. M. Rezende; Viviana M. Camelo-García; Sónia C. S. Andrade; José E. Buriolla; Elliot W. Kitajima; Ligia M. L. Duarte (Archives of Virology, 2017)

Physiological differences and changes in global DNA methylation levels in Agave angustifolia Haw. albino variant somaclones during the micropropagation process - Fátima Duarte-Aké; Eduardo Castillo-Castro; Felipe Barredo Pool; Francisco Espadas; Jorge M. Santamaría; Manuel L. Robert; Clelia De-la-Peña (Plant Cell Reports, 2016)

Music supported therapy promotes motor plasticity in individuals with chronic stroke - P. Ripollés; N. Rojo; J. Grau-Sánchez; J. L. Amengual; E. Càmara; J. Marco-Pallarés; M. Juncadella; L. Vaquero; F. Rubio; E. Duarte; C. Garrido; E. Altenmüller; et al. (Brain Imaging and Behavior, 2016)

New jacaranone glucoside from Jacaranda oxyphylla leaves - V. V. Pereira; L. P. Duarte; R. R. Silva; J. A. Takahashi (Natural Product Research, 2016)

Prevalence of the genus Cladosporium on the integument of leaf-cutting ants characterized by 454 pyrosequencing - A. P. M. Duarte; M. Ferro; A. Rodrigues; M. Bacci; N. S. Nagamoto; L. C. Forti; F. C. Pagnocca (Antonie van Leeuwenhoek, 2016)

Modulation of aquaporins 3 and 9 after exposure of ovine ovarian tissue to cryoprotectants followed by in vitro culture - A. D. Sales; A. B. G. Duarte; R. R. Santos; K. A. Alves; L. F. Lima; G. Q. Rodrigues; I. R. Brito; C. H. Lobo; J. B. Bruno; Y. Locatelli; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Research, 2016)

Lethal neonatal meningoencephalitis caused by multi-drug resistant, highly virulent Escherichia coli - Junaid Iqbal; Kevin R. Dufendach; John C. Wellons; Maria G. Kuba; Hilary H. Nickols; Oscar G. Gómez-Duarte; James L. Wynn (Infectious Diseases, 2016)

Biofortification of wheat, rice and common bean by applying foliar zinc fertilizer along with pesticides in seven countries - H. Ram; A. Rashid; W. Zhang; A. P. Duarte; N. Phattarakul; S. Simunji; M. Kalayci; R. Freitas; B. Rerkasem; R. S. Bal; K. Mahmood; E. Savasli; et al. (Plant and Soil, 2016)

Assessing soil erosion risk using RUSLE through a GIS open source desktop and web application - L. Duarte; A. C. Teodoro; J. A. Gonçalves; D. Soares; M. Cunha (Environmental Monitoring and Assessment, 2016)

Sewage sludge hazardous assessment: chemical evaluation and cytological effects in CHO-k1 cells - M. M. Bonomo; M. Morozesk; I. D. Duarte; L. D. Rocha; M. N. Fernandes; S. T. Matsumoto (Environmental Science and Pollution Research, 2016)

Testing the climate variability hypothesis in thermal tolerance limits of tropical and temperate tadpoles - L. M. Gutiérrez‐Pesquera; M. Tejedo; M. Á. Olalla‐Tárraga; H. Duarte; A. Nicieza; M. Solé (Journal of Biogeography, 2016)
Aim The climate variability hypothesis ( CVH ) states that a positive relationship may exist between the breadth of thermal tolerance range and the level of climatic variability experienced by taxa with increasing latitude, especially in terrestrial ectotherms. Under CVH , we expected to find a correspondence between both thermal tolerance limits ( CT max and CT min), ambient extreme temperature and the range sizes of species. We examined the validity of these predictions in a lowland tropical and a temperate tadpole assemblage. Location Lowland Neotropics (Bahia, Brazil) and Palaearctic (Iberian Peninsula and North Africa). Method We employed phylogenetic eigenvector regression ( PVR ) and Pagel's lambda to analyse phylogenetic signals in CT max and CT min. We used phylogenetic regression analyses ( PGLS ) to test the relationships between thermal limits, range size and temperature predictors (measured at the macroscale and microhabitat levels) and phy‐ ANOVA to compare both the physiological traits and thermal regimen in both tropical and temperate assemblages. Results We documented moderate‐to‐strong phylogenetic signal in both heat and cold tolerance. Temperate‐zone tadpoles had broader thermal tolerances than tropical ones. Thermal tolerance range was correlated with range sizes and was explained by seasonal thermal range predictors at the global scale. Both macro‐ and microclimate temperature variables provided the best predictive multivariate models of thermal limits at the global scale. Microclimatic predictors, however, were the main determinants of CT max and CT min variation at the local level of tropical and temperate communities respectively. Main conclusions Thermal tolerance range increases with latitude in tadpoles due to the higher increase in cold tolerance in temperate tadpoles. At the global scale, both macro‐ and microenvironment thermal information were reliable predictors of critical thermal limits and thermal tolerance range, as CVH predicts. However, thermal limits were best predicted by temperatures of the micro‐habitat at the regional level, thus suggesting that physiological thermal boundaries may be governed by thermal selection.

The concerted impact of domestication and transposon insertions on methylation patterns between dogs and grey wolves - Ilana Janowitz Koch; Michelle M. Clark; Michael J. Thompson; Kerry A. Deere‐Machemer; Jun Wang; Lionel Duarte; Gitanjali E. Gnanadesikan; Eskender L. McCoy; Liudmilla Rubbi; Daniel R. Stahler; Matteo Pellegrini; Elaine A. Ostrander; et al. (Molecular Ecology, 2016)
The process of domestication can exert intense trait‐targeted selection on genes and regulatory regions. Specifically, rapid shifts in the structure and sequence of genomic regulatory elements could provide an explanation for the extensive, and sometimes extreme, variation in phenotypic traits observed in domesticated species. Here, we explored methylation differences from >24 000 cytosines distributed across the genomes of the domesticated dog ( Canis familiaris ) and the grey wolf ( Canis lupus ). PCA and model‐based cluster analyses identified two primary groups, domestic vs. wild canids. A scan for significantly differentially methylated sites ( DMS s) revealed species‐specific patterns at 68 sites after correcting for cell heterogeneity, with weak yet significant hypermethylation typical of purebred dogs when compared to wolves (59% and 58%, P 66%) of differentially methylated regions contained or were associated with repetitive elements, indicative of a genotype‐mediated trend. However, DMS s were also often linked to functionally relevant genes (e.g. neurotransmitters). Finally, we utilized known genealogical relationships among Yellowstone wolves to survey transmission stability of methylation marks, from which we found a substantial fraction that demonstrated high heritability (both H 2 and h 2 > 0.99). These analyses provide a unique epigenetic insight into the molecular consequences of recent selection and radiation of our most ancient domesticated companion, the dog. These findings suggest selection has acted on methylation patterns, providing a new genomic perspective on phenotypic diversification in domesticated species.

The impact of interpersonal pre-warning information dissemination on regional emergency evacuation - N. Zhang; X. Y. Ni; H. Huang; J. L. Zhao; M. Duarte; J. Zhang (Natural Hazards, 2016)

Rhizopus arrhizus and Fusarium solani Concomitant Infection in an Immunocompromised Host - João N. de Almeida Júnior; Karim Y. Ibrahim; Gilda M. B. Del Negro; Evandro D. Bezerra; Amaro N. Duarte Neto; Marjorie V. Batista; Rinaldo F. Siciliano; Mauro C. Giudice; Adriana L. Motta; Flávia Rossi; Ligia C. Pierrotti; Maristela P. Freire; et al. (Mycopathologia, 2016)

Potato virus Y infection affects flavonoid profiles of Physalis angulata L. - Alice Nagai; Lígia M. L. Duarte; Alexandre L. R. Chaves; Déborah Y. A. C. dos Santos (Brazilian Journal of Botany, 2015)

Phytoremediation of Heavy Metal-Contaminated Soils Using the Perennial Energy Crops Miscanthus spp. and Arundo donax L. - Bruno Barbosa; Sara Boléo; Sarah Sidella; Jorge Costa; Maria Paula Duarte; Benilde Mendes; Salvatore L. Cosentino; Ana Luisa Fernando (BioEnergy Research, 2015)

A global meta‐analysis of the relative extent of intraspecific trait variation in plant communities - Andrew Siefert; Cyrille Violle; Loïc Chalmandrier; Cécile H. Albert; Adrien Taudiere; Alex Fajardo; Lonnie W. Aarssen; Christopher Baraloto; Marcos B. Carlucci; Marcus V. Cianciaruso; Vinícius de L. Dantas; Francesco de Bello; et al. (Ecology Letters, 2015)
Recent studies have shown that accounting for intraspecific trait variation ( ITV ) may better address major questions in community ecology. However, a general picture of the relative extent of ITV compared to interspecific trait variation in plant communities is still missing. Here, we conducted a meta‐analysis of the relative extent of ITV within and among plant communities worldwide, using a data set encompassing 629 communities (plots) and 36 functional traits. Overall, ITV accounted for 25% of the total trait variation within communities and 32% of the total trait variation among communities on average. The relative extent of ITV tended to be greater for whole‐plant (e.g. plant height) vs. organ‐level traits and for leaf chemical (e.g. leaf N and P concentration) vs. leaf morphological (e.g. leaf area and thickness) traits. The relative amount of ITV decreased with increasing species richness and spatial extent, but did not vary with plant growth form or climate. These results highlight global patterns in the relative importance of ITV in plant communities, providing practical guidelines for when researchers should include ITV in trait‐based community and ecosystem studies.

Mesoscale variability in the Arabian Sea from HYCOM model results and observations: impact on the Persian Gulf Water path - P. L'Hégaret; R. Duarte; X. Carton; C. Vic; D. Ciani; R. Baraille; S. Corréard (Ocean Science, 2015)
The Arabian Sea and Sea of Oman circulation and water masses, subject to monsoon forcing, reveal a strong seasonal variability and intense mesoscale features. We describe and analyze this variability and these features, using both meteorological data (from ECMWF reanalyses), in situ observations (from the ARGO float program and the GDEM – Generalized Digital Environmental mode – climatology), satellite altimetry (from AVISO) and a regional simulation with a primitive equation model (HYCOM – the Hybrid Coordinate Ocean Model). The model and observations display comparable variability, and the model is then used to analyze the three-dimensional structure of eddies and water masses with higher temporal and spatial resolutions than the available observations. The mesoscale features are highly seasonal, with the formation of coastal currents, destabilizing into eddies, or the radiation of Rossby waves from the Indian coast. The mesoscale eddies have a deep dynamical influence and strongly drive the water masses at depth. In particular, in the Sea of Oman, the Persian Gulf Water presents several offshore ejection sites and a complex recirculation, depending on the mesoscale eddies. The associated mechanisms range from coastal ejection via dipoles, alongshore pulses due to a cyclonic eddy, to the formation of lee eddies downstream of Ra's Al Hamra. This water mass is also captured inside the eddies via several mechanisms, keeping high thermohaline characteristics in the Arabian Sea. The variations of the outflow characteristics near the Strait of Hormuz are compared with variations downstream.

Nickel and Copper Toxicity to Embryos of the Long-Spined Sea Urchin, Diadema savignyi - G. Rosen; I. Rivera-Duarte; M. A. Colvin; R. E. Dolecal; L. J. Raymundo; P. J. Earley (Bulletin of Environmental Contamination and Toxicology, 2015)

Recurrent patterns of phylogenetic habitat filtering in woody plant communities across phytogeographically distinct grassland-forest ecotones - V. J. Debastiani; S. C. Muller; J. M. Oliveira; F. S. Rocha; M. C. Sestren-Bastos; L. D. S. Duarte (Community Ecology, 2015)

The antiatherogenic effect of bixin in hypercholesterolemic rabbits is associated to the improvement of lipid profile and to its antioxidant and anti-inflammatory effects - Sabrina Somacal; Cassieli G. Figueiredo; Andréia Quatrin; Amanda R. Ruviaro; Lisiane Conte; Paula R. Augusti; Miguel Roehrs; Ione T. Denardin; Jocieli Kasten; Marcelo L. da Veiga; Marta M. F. Duarte; Tatiana Emanuelli (Molecular and Cellular Biochemistry, 2015)

Phylogeny and recombination analysis of Brazilian yellow passion fruit isolates of Cowpea aphid-borne mosaic virus: origin and relationship with hosts - Leilane K. Rodrigues; Leonardo A. Silva; Renata M. Garcêz; Alexandre L. R. Chaves; Ligia M. L. Duarte; José S. Giampani; Addolorata Colariccio; Ricardo Harakava; Marcelo Eiras (Australasian Plant Pathology, 2015)

Yield and water productivity of five chickpea varieties under supplemental irrigation in contrasting years - L. L. Silva; I. Duarte; E. Lourenço; N. Simões; M. M. Chaves (Irrigation Science, 2014)

Mercury accumulation and tissue-specific antioxidant efficiency in the wild European sea bass (Dicentrarchus labrax) with emphasis on seasonality - C. L. Mieiro; M. Dolbeth; T. A. Marques; A. C. Duarte; M. E. Pereira; M. Pacheco (Environmental Science and Pollution Research, 2014)

Leaf-cutting ants: an unexpected microenvironment holding human opportunistic black fungi - A. P. M. Duarte; D. Attili-Angelis; N. C. Baron; L. C. Forti; F. C. Pagnocca (Antonie van Leeuwenhoek, 2014)

Highly polymorphic microsatellite markers for the Mediterranean endemic fan mussel Pinna nobilis - M. GONZALEZ-WANGUEMERT; J. COSTA; L. BASSO; C. DUARTE; E. SERRÃO; I. HENDRIKS (Mediterranean Marine Science, 2014)
Pinna nobilis is an endemic bivalve of the Mediterranean Sea whose populations have decreased in the last decades due to human pressure; as consequence, it was declared a protected species in 1992. Despite its conservation status, few genetic studies using mitochondrial markers have been published. We report on the isolation and development of 10 microsatellite loci for the fan mussel, Pinna nobilis. All loci (2 di-nucleotide, 5 tri-nucleotide, 2 tetra-nucleotide and 1 penta-nucleotide) are characterized by high polymorphism levels in 76 individuals tested from two populations in Balearic Islands (Spain, Western Mediterranean Sea). Number of alleles ranged from 4 to 24 and expected heterozygosity ranged from 0.4269 to 0.9400. These microsatellites could be very useful to assess the genetic diversity and connectivity patterns of P. nobilis and to establish new conservation strategies.

Gelatinous zooplankton biomass in the global oceans: geographic variation and environmental drivers - Cathy H. Lucas; Daniel O. B. Jones; Catherine J. Hollyhead; Robert H. Condon; Carlos M. Duarte; William M. Graham; Kelly L. Robinson; Kylie A. Pitt; Mark Schildhauer; Jim Regetz (Global Ecology and Biogeography, 2014)
Aim Scientific debate regarding the future trends, and subsequent ecological, biogeochemical and societal impacts, of gelatinous zooplankton ( GZ ) in a changing ocean is hampered by lack of a global baseline and an understanding of the causes of biogeographic patterns. We address this by using a new global database of GZ records to test hypotheses relating to environmental drivers of biogeographic variation in the multidecadal baseline of epipelagic GZ biomass in the world's oceans. Location Global oceans. Methods Over 476,000 global GZ data and metadata items were assembled from a variety of published and unpublished sources. From this, a total of 91,765 quantitative abundance data items from 1934 to 2011 were converted to carbon biomass using published biometric equations and species‐specific average sizes. Total GZ , Cnidaria, Ctenophora and Chordata (Thaliacea) biomass was mapped into 5° grid cells and environmental drivers of geographic variation were tested using spatial linear models. Results We present JeDI (the J ellyfish D atabase I nitiative), a publically accessible database available at http://jedi.nceas.ucsb.edu . We show that: (1) GZ are present throughout the world's oceans; (2) the global geometric mean and standard deviation of total gelatinous biomass is 0.53 ± 16.16 mg C m −3 , corresponding to a global biomass of 38.3 Tg C in the mixed layer of the ocean; (3) biomass of all gelatinous phyla is greatest in the subtropical and boreal Northern Hemisphere; and (4) within the North Atlantic, dissolved oxygen, apparent oxygen utilization and sea surface temperature are the principal drivers of biomass distribution. Main conclusions JeDI is a unique global dataset of GZ taxa which will provide a benchmark against which future observations can be compared and shifting baselines assessed. The presence of GZ throughout the world's oceans and across the complete global spectrum of environmental variables indicates that evolution has delivered a range of species able to adapt to all available ecological niches.

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Plasmopara invertifolia sp. nov. causing downy mildew on Helichrysum bracteatum (Asteraceae) - Lidiane L. Duarte; Young-Joon Choi; Dartanhã J. Soares; Robert W. Barreto (Mycological Progress, 2014)

Sponge-microbialite buildups from the Toarcian of the Coimbra region (Northern Lusitanian Basin, Portugal): paleoecological and paleoenvironmental significance - Matías Reolid; L. V. Duarte (Facies, 2014)

Climate effects on amphibian distributions depend on phylogenetic resolution and the biogeographical history of taxa - L. D. S. Duarte; C. Both; V. J. Debastiani; M. B. Carlucci; L. O. Gonçalves; L. Cappelatti; G. D. S. Seger; V. A. G. Bastazini; F. T. Brum; E. V. Salengue; J. S. Bernardo‐Silva (Global Ecology and Biogeography, 2014)
Aim Disentangling the effects of climate and historical factors on biodiversity distribution remains a challenge for biogeographers. Here, we provide an analytical framework to discriminate the contributions of contemporary climate and the biogeographical history of taxa to the geographical distributions of phylogenetic lineages. Furthermore, we evaluate the constraint that the biogeographical history of clades exerts on the association between climate and clade distribution, i.e. the historical legacy of climatic effects. As a case study, we analysed the distributions of amphibian lineages across the A mericas. Location The A mericas. Methods We tallied the number of amphibian species per genus in each of 262 ecoregions. Each ecoregion was described by the composition of phylogenetic lineages using phylogenetic fuzzy weighting. The composition of amphibian genera and phylogenetic clades represented the distributions of shallow and deep phylogenetic nodes, respectively. We characterized each ecoregion by the biogeographical history of amphibian taxa and its current climate, whose influences on shallow and deep phylogenetic nodes were analysed using variation partitioning analysis. Results The association between climate and the distributions of deep phylogenetic nodes showed a strong historical legacy, although the distribution of amphibian genera was mostly associated with climate. Hyloidea were associated with a G ondwanan origin and higher annual mean temperatures, whereas other clades (e.g. C audata) were related to a L aurasian origin and higher temperature seasonality. Microhylidae were related to occurrence in the E arly J urassic in G ondwana and recent occurrence in the N eotropics. Main conclusions Biogeographical patterns can be thought of as the net outcome of evolutionary, historical and ecological processes. Although temperature is likely to affect the ecology of amphibians, the effects of climate on the distributions of deep phylogenetic nodes were strongly constrained by the biogeographical history of clades. Nevertheless, local, climatically driven processes are likely to influence the distributions of shallow phylogenetic nodes. The historical biogeography of clades might help to explain the interplay between evolutionary and environmental processes in determining assembly patterns found elsewhere.

Life cycle contributions of copper from vessel painting and maintenance activities - Patrick J. Earley; Brandon L. Swope; Katherine Barbeau; Randelle Bundy; Janessa A. McDonald; Ignacio Rivera-Duarte (Biofouling, 2014)

Palynofacies and TOC analysis of marine and non-marine sediments across the Middle–Upper Jurassic boundary in the central-northern Lusitanian Basin (Portugal) - Ricardo L. Silva; João G. Mendonça Filho; Ana C. Azerêdo; Luís V. Duarte (Facies, 2014)

Taxonomic assessment and enzymes production by yeasts isolated from marine and terrestrial Antarctic samples - A. W. F. Duarte; I. Dayo-Owoyemi; F. S. Nobre; F. C. Pagnocca; L. C. S. Chaud; A. Pessoa; M. G. A. Felipe; L. D. Sette (Extremophiles, 2013)

Habitat monitoring and genotoxicity in Ucides cordatus (Crustacea: Ucididae), as tools to manage a mangrove reserve in southeastern Brazil - M. A. A. Pinheiro; L. F. A. Duarte; T. R. Toledo; M. L. Adam; R. A. Torres (Environmental Monitoring and Assessment, 2013)

Antibacterial activity of alkaloids produced by endophytic fungus Aspergillus sp. EJC08 isolated from medical plant Bauhinia guianensis - Eduardo Antonio A. Pinheiro; Josiwander Miranda Carvalho; Diellem Cristina P. dos Santos; André de Oliveira Feitosa; Patrícia Santana B. Marinho; Giselle Maria Skelding Pinheiro Guilhon; Afonso Duarte L. de Souza; Felipe Moura A. da Silva; Andrey Moacir do R. Marinho (Natural Product Research, 2013)

Long-distance lava correlation in the Paraná volcanic province along the Serra Geral cuesta, southeastern Brazil - L. A. Hartmann; K. R. Arena; S. K. Duarte; J. Pertille (International Journal of Earth Sciences, 2013)

Core–shell magnetite-silica dithiocarbamate-derivatised particles achieve the Water Framework Directive quality criteria for mercury in surface waters - C. B. Lopes; P. Figueira; D. S. Tavares; Z. Lin; A. L. Daniel-da-Silva; A. C. Duarte; J. Rocha; T. Trindade; E. Pereira (Environmental Science and Pollution Research, 2013)

Calibration and validation of SALTMED model under dry and wet year conditions using chickpea field data from Southern Portugal - L. L. Silva; R. Ragab; I. Duarte; E. Lourenço; N. Simões; M. M. Chaves (Irrigation Science, 2013)

Influence of red wine fermentation oenological additives on inoculated strain implantation - Filomena L. Duarte; Ana Claudia Alves; Maria Filomena Alemão; M. Margarida Baleiras-Couto (World Journal of Microbiology and Biotechnology, 2013)

Species‐specific ontogenetic diet shifts among Neotropical Crenicichla : using stable isotopes and tissue stoichiometry - E. D. Burress; A. Duarte; W. S. Serra; M. M. Gangloff; L. Siefferman (Journal of Fish Biology, 2013)
Ontogenetic diet shifts were compared among five sympatric pike cichlids Crenicichla in a subtropical South American stream using stable C and N isotopes and tissue stoichiometry (C:N). Within species, stable N isotopes were positively related to body size while C:N showed negative relationships. Stable C isotopes, however, were not related to body size in any species. By modelling the switch to piscivory using gut content‐isotope‐body size relationships, diet shifts were shown to be species‐specific with regard to both rate and degree of piscivory. Compared to other piscivorous lineages, Crenicichla appear to be unusually small‐bodied (based on maximum body size). Because of their diversity, abundance and dynamic size‐structured functional roles, Crenicichla may exert broad and complex predation pressures on the aquatic community.

Impacts of ocean acidification on marine organisms: quantifying sensitivities and interaction with warming - Kristy J. Kroeker; Rebecca L. Kordas; Ryan Crim; Iris E. Hendriks; Laura Ramajo; Gerald S. Singh; Carlos M. Duarte; Jean‐Pierre Gattuso (Global Change Biology, 2013)
Ocean acidification represents a threat to marine species worldwide, and forecasting the ecological impacts of acidification is a high priority for science, management, and policy. As research on the topic expands at an exponential rate, a comprehensive understanding of the variability in organisms' responses and corresponding levels of certainty is necessary to forecast the ecological effects. Here, we perform the most comprehensive meta‐analysis to date by synthesizing the results of 228 studies examining biological responses to ocean acidification. The results reveal decreased survival, calcification, growth, development and abundance in response to acidification when the broad range of marine organisms is pooled together. However, the magnitude of these responses varies among taxonomic groups, suggesting there is some predictable trait‐based variation in sensitivity, despite the investigation of approximately 100 new species in recent research. The results also reveal an enhanced sensitivity of mollusk larvae, but suggest that an enhanced sensitivity of early life history stages is not universal across all taxonomic groups. In addition, the variability in species' responses is enhanced when they are exposed to acidification in multi‐species assemblages, suggesting that it is important to consider indirect effects and exercise caution when forecasting abundance patterns from single‐species laboratory experiments. Furthermore, the results suggest that other factors, such as nutritional status or source population, could cause substantial variation in organisms' responses. Last, the results highlight a trend towards enhanced sensitivity to acidification when taxa are concurrently exposed to elevated seawater temperature.

Anxiogenic-like profile of Wistar adult rats based on the pilocarpine model: an animal model for trait anxiety? - Filipe S. Duarte; Marcelo Duzzioni; Alexandre A. Hoeller; Nayana M. Silva; Andy L. Ern; Tetsade C. Piermartiri; Carla I. Tasca; Elaine C. Gavioli; Tadeu Lemos; Antonio P. Carobrez; Thereza C. M. De Lima (Psychopharmacology, 2013)

Susceptibility of Forests in the Northeastern USA to Nitrogen and Sulfur Deposition: Critical Load Exceedance and Forest Health - N. Duarte; L. H. Pardo; M. J. Robin-Abbott (Water, Air, & Soil Pollution, 2013)

Inferring groundwater contributions and pathways to streamflow during snowmelt over multiple years in a discontinuous permafrost subarctic environment (Yukon, Canada) - Sean K. Carey; Jessica L. Boucher; Celina M. Duarte (Hydrogeology Journal, 2013)

Hydroid assemblages across the A tlantic– M editerranean boundary: is the S trait of G ibraltar a marine ecotone? - Manuel M. González‐Duarte; Cesar Megina; Stefano Piraino; Juan L. Cervera (Marine Ecology, 2013)
Strong gradients in physico‐chemical properties between abutting water masses create prominent transition zones in the marine environment. The S trait of G ibraltar forms the well defined boundary between the M editerranean and A tlantic, and this paper examines spatial variation of hydroid assemblages in this transition zone. Although several studies highlighted the transitional character of the Strait and defined it as an ecotone, the benthic hydroid assemblages did not show differences between the G ulf of C ádiz and the A lboran S ea. However, there is an asymmetrical influence of the Atlantic waters on the coastal benthic ecosystems of the A lboran S ea, which maintains a more Mediterranean character in the hydroid assemblages of the northern coast, whereas a more A tlantic character was found in the rest of the studied sites. The transition zone between A tlantic and M editerranean benthic communities could be associated with an A tlantic I nfluence Z one rather than with the S trait of G ibraltar itself.

Hematological indices and activity of NTPDase and cholinesterase enzymes in rats exposed to cadmium and treated with N-acetylcysteine - Jamile F. Gonçalves; Marta M. M. F. Duarte; Amanda M. Fiorenza; Roselia M. Spanevello; Cinthia M. Mazzanti; Roberta Schmatz; Margarete D. Bagatini; Fabiane G. Antes; Pauline Costa; Fátima H. Abdalla; Valderi L. Dressler; Vera M. Morsch; et al. (BioMetals, 2012)

Pesticide application to agricultural fields: effects on the reproduction and avoidance behaviour of Folsomia candida and Eisenia andrei - M. J. G. Santos; M. F. L. Ferreira; A. Cachada; A. C. Duarte; J. P. Sousa (Ecotoxicology, 2012)

Saccharomyces bacillaris is not a synonym of Candida stellata: reinstatement as Starmerella bacillaris comb. nov. - F. L. Duarte; N. H. Pimentel; A. Teixeira; Á. Fonseca (Antonie van Leeuwenhoek, 2012)

Net primary productivity, upwelling and coastal currents in the Gulf of Ulloa, Baja California, México - E. González-Rodríguez; A. Trasviña-Castro; G. Gaxiola-Castro; L. Zamudio; R. Cervantes-Duarte (Ocean Science, 2012)
The Gulf of Ulloa, a highly productive area off the western coast of the Baja California Peninsula, is examined for five successive years (2003–2007) by using satellite data and seasonal net primary productivity (NPP) estimates obtained from a vertical generalised production model. The results identify that northwestern winds blow parallel to the coast throughout the year. However, highest NPP occurs from March to June. During this period, an equatorward coastal current transports water from neighbouring upwelling areas to the northern Gulf of Ulloa and in combination with local upwelling, which injects nutrients into the euphotic zone, produce the observed increase in NPP. The opposite situation occurs in late summer when a warm poleward current of tropical characteristics arrives and inhibits the productivity in the whole region and generates the yearly lowest NPP levels. Our findings reveal the importance of lateral advection in the modulation of the primary productivity in this subtropical upwelling region.

Evaluation of Species-Specific Dissimilarities in Two Marine Fish Species: Mercury Accumulation as a Function of Metal Levels in Consumed Prey - C. L. Mieiro; J. P. Coelho; M. Pacheco; A. C. Duarte; M. E. Pereira (Archives of Environmental Contamination and Toxicology, 2012)

Persistence of uropathogenic Escherichia coli strains in the host for long periods of time: relationship between phylogenetic groups and virulence factors - A. Narciso; F. Nunes; T. Amores; L. Lito; J. Melo-Cristino; A. Duarte (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

First histological and virological report of fibropapilloma associated with herpesvirus in Chelonia mydas at Príncipe Island, West Africa - A. Duarte; P. Faísca; N. S. Loureiro; R. Rosado; S. Gil; N. Pereira; L. Tavares (Archives of Virology, 2012)

Olive oil mill wastewaters before and after treatment: a critical review from the ecotoxicological point of view - Celine I. L. Justino; Ruth Pereira; Ana C. Freitas; Teresa A. P. Rocha-Santos; Teresa S. L. Panteleitchouk; Armando C. Duarte (Ecotoxicology, 2012)

The field resistance of potato cultivars to foliar late blight and its relationship with foliage maturity type and skin type in Brazil - H. S. S. Duarte; L. Zambolim; E. S. G. Mizubuti; J. G. Pádua; J. I. Ribeiro Júnior; E. L. Carmo; A. F. Nogueira Júnior (Australasian Plant Pathology, 2012)

Coordination of lapachol to bismuth(III) improves its anti-inflammatory and anti-angiogenic activities - Gabrieli L. Parrilha; Rafael P. Vieira; Paula P. Campos; Grácia Divina F. Silva; Lucienir P. Duarte; Silvia P. Andrade; Heloisa Beraldo (BioMetals, 2012)

Sodium Fluxes in Tamoatá, Hoplosternum litoralle, Exposed to Formation Water from Urucu Reserve (Amazon, Brazil) - Bernardo Baldisserotto; Luciano O. Garcia; Ana Paula Benaduce; Rafael M. Duarte; Thiago L. Nascimento; Levy C. Gomes; Adriana R. Chippari Gomes; Adalberto L. Val (Archives of Environmental Contamination and Toxicology, 2012)

The impact of logging on the surrounding flow in a managed forest - Gengsheng Zhang; Monique Y. Leclerc; Anandakumar Karipot; Henrique F. Duarte; Erich Mursch-Radlgruber; Henry L. Gholz (Theoretical and Applied Climatology, 2011)

Edge expansion of Araucaria forest over southern Brazilian grasslands relies on nurse plant effect - M. Carlucci; F. Teixeira; F. Brum; L. Duarte (Community Ecology, 2011)

Early-life environmental intervention may increase the number of neurons, astrocytes, and cellular proliferation in the hippocampus of rats - Elisa C. Winkelmann-Duarte; Camila B. Padilha-Hoffmann; Daniel F. Martins; Artur F. S. Schuh; Marilda C. Fernandes; Ricardo Santin; Suelen Merlo; Gilberto L. Sanvitto; Aldo B. Lucion (Experimental Brain Research, 2011)

Determination and Evaluation of the Mineral Composition of Obi (Cola acuminate) - Valdinei S. Martins; Raildo M. de Jesus; Erik G. P. da Silva; Wallace Duarte Fragoso; Sérgio L. C. Ferreira (Biological Trace Element Research, 2011)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

In vitro transference and molecular characterization of bla TEM genes in bacteria isolated from Portuguese ready-to-eat foods - P. Amador; R. Fernandes; I. Duarte; L. Brito; C. Prudêncio (World Journal of Microbiology and Biotechnology, 2011)

Pyriculariopsis calatheae sp. nov., a novel anamorphic hyphomycete from the Atlantic forest of Brazil causing leaf spots on Calathea longifolia - Dartanhã J. Soares; Fabiano B. Rocha; Lidiane L. Duarte; Robert W. Barreto (Mycological Progress, 2011)

Plant diaspore traits as indicators of mutualistic interactions in woody vegetation patches developing into a grassland-forest mosaic - L. Duarte; M. Carlucci; C. Fontana; S. Hartz; V. Pillar (Community Ecology, 2011)

The small nuclear ribonucleoprotein U1A interacts with NS5 from yellow fever virus - Roberta V. M. Bronzoni; Maria C. F. S. Madrid; Danilo V. B. Duarte; Vanessa O. A. Pellegrini; Carolina C. Pacca; Ana C. V. Carmo; Cleslei F. Zanelli; Sandro R. Valentini; Carolina Santacruz-Pérez; João A. R. G. Barbosa; Carol S. Lutz; Paula Rahal; et al. (Archives of Virology, 2011)

Sleeping Site Selection by Urban Marmosets (Callithrix penicillata) Under Conditions of Exceptionally High Predator Density - Marina H. L. Duarte; Robert J. Young (International Journal of Primatology, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Effect of ice melting on bacterial carbon fluxes channelled by viruses and protists in the Arctic Ocean - Julia A. Boras; M. Montserrat Sala; Jesus M. Arrieta; Elisabet L. Sà; Jorge Felipe; Susana Agustí; Carlos M. Duarte; Dolors Vaqué (Polar Biology, 2010)

Perinatal l-arginine and antioxidant supplements reduce adult blood pressure but not ameliorate the altered vascular function in spontaneously hypertensive rats - Diego B. de Queiroz; Fernanda E. Ramos-Alves; Raphaella L. Fernandes; Cíntia P. Zuzu; Glória P. Duarte; Fabiano E. Xavier (Journal of Physiology and Biochemistry, 2010)

Finding Geological Heritage: Legal Issues on Private Property and Fieldwork. The Case of Outstanding Early Angiosperms (Barremian to Albian, Portugal) - Jorge L. Dinis; Fernanda P. Oliveira; Jacques Rey; Isabel L. Duarte (Geoheritage, 2010)

Allelochemical Effects of Volatile Compounds and Organic Extracts from Muscodor yucatanensis, a Tropical Endophytic Fungus from Bursera simaruba - Martha L. Macías-Rubalcava; Blanca E. Hernández-Bautista; Fabiola Oropeza; Georgina Duarte; María C. González; Anthony E. Glenn; Richard T. Hanlin; Ana Luisa Anaya (Journal of Chemical Ecology, 2010)

Antioxidant system breakdown in brain of feral golden grey mullet (Liza aurata) as an effect of mercury exposure - C. L. Mieiro; I. Ahmad; M. E. Pereira; A. C. Duarte; M. Pacheco (Ecotoxicology, 2010)

Genetic similarity among genotypes of sugarcane estimated by SSR and coefficient of parentage - L. S. C. Duarte Filho; P. P. Silva; J. M. Santos; G. V. S. Barbosa; C. E. Ramalho-Neto; L. Soares; J. C. F. Andrade; C. Almeida (Sugar Tech, 2010)

Seed removal patterns by vertebrates in different successional stages of Araucaria forest advancing over southern Brazilian grasslands - F. Brum; L. Duarte; S. Hartz (Community Ecology, 2010)

Subtidal stromatolites from the Sinemurian of the Lusitanian Basin (Portugal) - Ana C. Azerêdo; Ricardo L. Silva; Luís V. Duarte; M. Cristina Cabral (Facies, 2010)

An NMR structural study of nickel-substituted rubredoxin - Brian J. Goodfellow; Iven C. N. Duarte; Anjos L. Macedo; Brian F. Volkman; Sofia G. Nunes; I. Moura; John L. Markley; José J. G. Moura (JBIC Journal of Biological Inorganic Chemistry, 2010)

Effects of ECF-Kraft pulp mill effluent treated with fungi (Rhizopus oryzae) on reproductive steroids and liver CYP1A of exposed goldfish (Carassius auratus) - M. S. Diniz; I. Peres; L. Castro; A. C. Freitas; T. A. P. Rocha-Santos; P. M. Costa; R. Pereira; A. C. Duarte (Ecotoxicology, 2009)

Identification of up-regulated genes in flag leaves during rice grain filling and characterization of OsNAC5, a new ABA-dependent transcription factor - Raul A. Sperotto; Felipe K. Ricachenevsky; Guilherme L. Duarte; Tatiana Boff; Karina L. Lopes; Edilena R. Sperb; Michael A. Grusak; Janette Palma Fett (Planta, 2009)

Spatial Variability of Trace Metals and Inorganic Nutrients in Surface Waters of Todos Santos Bay, México in the Summer of 2005 During a Red Tide Algal Bloom - M. L. Lares; S. G. Marinone; I. Rivera-Duarte; A. Beck; S. Sañudo-Wilhelmy (Archives of Environmental Contamination and Toxicology, 2009)

Fraction images derived from Terra Modis data for mapping burnt areas in Brazilian Amazonia - Y. E. Shimabukuro; V. Duarte; E. Arai; R. M. Freitas; A. Lima; D. M. Valeriano; I. F. Brown; M. L. R. Maldonado (International Journal of Remote Sensing, 2009)

Foliar application of potassium silicate reduces the intensity of soybean rust - F. A. Rodrigues; H. S. S. Duarte; G. P. Domiciano; C. A. Souza; G. H. Korndörfer; L. Zambolim (Australasian Plant Pathology, 2009)

Trophic Transfers from Seagrass Meadows Subsidize Diverse Marine and Terrestrial Consumers - Kenneth L. Heck; Tim J. B. Carruthers; Carlos M. Duarte; A. Randall Hughes; Gary Kendrick; Robert J. Orth; Susan W. Williams (Ecosystems, 2008)

Evaluation of the microbial diversity in a horizontal-flow anaerobic immobilized biomass reactor treating linear alkylbenzene sulfonate - I. C. S. Duarte; L. L. Oliveira; N. K. D. Saavedra; F. Fantinatti-Garboggini; V. M. Oliveira; M. B. A. Varesche (Biodegradation, 2008)

First assessment of microbial diversity in faecal microflora of Eurasian otter (Lutra lutra Linnaeus, 1758) in Portugal - M. Oliveira; T. Sales-Luís; A. Duarte; S. F. Nunes; C. Carneiro; T. Tenreiro; R. Tenreiro; M. Santos-Reis; L. Tavares; C. L. Vilela (European Journal of Wildlife Research, 2008)

Sardine early survival, physical condition and stress after introduction to captivity - A. Marçalo; P. Pousão‐Ferreira; L. Mateus; J. H. Duarte Correia; Y. Stratoudakis (Journal of Fish Biology, 2008)
The main factors that affect early survival, physical damage and stress reactions of sardine Sardina pilchardus after live capture and introduction to captivity were examined. A total of 2800 sardines were captured alive from commercial purse seiners in five trials off southern Portugal and monitored for 4 weeks in aquaculture tanks. Survival rates varied considerably between trials (from 80% after a month), with most deaths occurring in the first 5 days. Sardine early survival was affected by factors related to conditions at sea (catch composition, sea temperature and transportation density), during introduction to captivity (magnitude of thermal shock, land transportation duration and use of antibacterial treatment) and, possibly, their interaction. Physical damage was related to the probability of dying, with fish that died during the first week showing significantly higher scale loss and larger caudal fin erosion that those that were alive in the same period. For all stress variables measured (blood haematocrit, cortisol, glucose and ions in the plasma), the most extreme values were attained during introduction to captivity or in the first hours after. After 2 weeks in captivity, most variables had returned to levels close to those observed at the onset of purse‐seine fishing, suggesting that maintenance conditions were adequate to permit a rapid recovery from fishing and transport stress.

Genetic structure of the diploid–polyploid fish Squalius alburnoides in southern Iberian basins Tejo and Guadiana, based on microsatellites - M. E. Crespo‐López; I. Pala; T. L. Duarte; T. E. Dowling; M. M. Coelho (Journal of Fish Biology, 2007)
Several studies have demonstrated the hybrid origin of Squalius alburnoides , a complex of diploid, triploid and tetraploid fish, with Squalius pyrenaicus as the maternal ancestor and an Anaecypris hispanica ‐like species as the paternal ancestor. The aim of this study was to assess patterns of genetic diversity and similarity between sympatric forms of the different ploidy levels of S. alburnoides and related parental species in the two largest basins that are part of its southern Iberian distribution, the Tejo and Guadiana, using microsatellites. High levels of genetic diversity were found in populations of S. alburnoides from both basins, reflecting the hybrid origin, the high diversity of forms in these river basins and the different modes of reproduction of the complex. Microsatellites indicated low values of genetic differentiation between the non‐hybrid all‐male form of S. alburnoides and A. hispanica , supporting the view that these forms share a common ancestor. In some instances, diploid and triploid hybrids from the same river basin were more closely related to each other than to their counterparts in the other basins, suggesting an ancient origin for the complex in these Iberian southern basins.

Effects of receptor density on Nociceptin/OrphaninFQ peptide receptor desensitisation: studies using the ecdysone inducible expression system - T. A. Barnes; J. McDonald; D. J. Rowbotham; T. L. Duarte; D. G. Lambert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effects of postural task requirements on the speed–accuracy trade-off - Marcos Duarte; Mark L. Latash (Experimental Brain Research, 2007)

Plumbing the Global Carbon Cycle: Integrating Inland Waters into the Terrestrial Carbon Budget - J. J. Cole; Y. T. Prairie; N. F. Caraco; W. H. McDowell; L. J. Tranvik; R. G. Striegl; C. M. Duarte; P. Kortelainen; J. A. Downing; J. J. Middelburg; J. Melack (Ecosystems, 2007)

Molecular characterization and antimicrobial activity of endophytic fungi from coffee plants - L. D. Sette; M. R. Z. Passarini; C. Delarmelina; F. Salati; M. C. T. Duarte (World Journal of Microbiology and Biotechnology, 2006)

Determination of Organic Mercury in Biota, Plants and Contaminated Sediments Using a Thermal Atomic Absorption Spectrometry Technique - M. Válega; S. Abreu; P. Pato; L. Rocha; A. R. Gomes; M. E. Pereira; A. C. Duarte (Water, Air, & Soil Pollution, 2006)

Unidirectional Sodium Fluxes and Gill CYP1A Induction in an Amazonian Fish (Hyphessobrycon erythrostigma) Exposed to a Surfactant and to Crude Oil - A. Y. O. Matsuo; R. M. Duarte; A. L. Val (Bulletin of Environmental Contamination and Toxicology, 2005)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE-Brazil II. Spatial and ontogenetic dynamics in Andira legalis, a deciduous legume tree - A. Geβler; H. M. Duarte; A. C. Franco; U. Lüttge; E. A. de Mattos; M. Nahm; F. R. Scarano; H. L. T. Zaluar; H. Rennenberg (Trees, 2005)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE Brazil I. Performance of three different species of Clusia in an array of plant communities - F. R. Scarano; H. M. Duarte; A. C. Franco; A. Geβler; E. A. de Mattos; M. Nahm; H. Rennenberg; H. L. T. Zaluar; U. Lüttge (Trees, 2005)

Within‐population spatial genetic structure, neighbourhood size and clonal subrange in the seagrass Cymodocea nodosa - FILIPE ALBERTO; LICÍNIA GOUVEIA; SOPHIE ARNAUD‐HAOND; JOSÉ L. PÉREZ‐LLORÉNS; CARLOS M. DUARTE; ESTER A. SERRÃO (Molecular Ecology, 2005)
The extent of clonality within populations strongly influences their spatial genetic structure (SGS), yet this is hardly ever thoroughly analysed. We employed spatial autocorrelation analysis to study effects of sexual and clonal reproduction on dispersal of the dioecious seagrass Cymodocea nodosa . Analyses were performed both at genet level (i.e. excluding clonal repeats) and at ramet level. Clonal structure was characterized by the clonal subrange, a spatial measure of the linear limits where clonality still affects SGS. We show that the clonal subrange is equivalent to the distance where the probability of clonal identity approaches zero. This combined approach was applied to two meadows with different levels of disturbance, Cadiz (stable) and Alfacs (disturbed). Genotypic richness, the proportion of the sample representing distinct genotypes, was moderate (0.38 Cadiz, 0.46 Alfacs) mostly due to dominance of a few clones. Expected heterozygosities were comparable to those found in other clonal plants. SGS analyses at the genet level revealed extremely restricted gene dispersal in Cadiz ( Sp = 0.052, a statistic reflecting the decrease of pairwise kinship with distance), the strongest SGS found for seagrass species, comparable only to values for selfing herbaceous land plants. At Cadiz the clonal subrange extended across shorter distances (20–25 m) than in Alfacs (30–35 m). Comparisons of sexual and vegetative components of gene dispersal suggest that, as a dispersal vector within meadows, clonal spread is at least as important as sexual reproduction. The restricted dispersal and SGS pattern in both meadows indicates that the species follows a repeated seedling recruitment strategy.

Lateral diffusion of CO2 in leaves of the crassulacean acid metabolism plant Kalancho daigremontiana Hamet et Perrier - Heitor M. Duarte; Ivona Jakovljevic; Friedemann Kaiser; Ulrich Lttge (Planta, 2005)

Variation of Mercury Contamination in Chicks of Little Tern Sterna albifrons in Southwest Europe: Brood, Age, and Colony Related Effects - P. C. Tavares; L. R. Monteiro; R. J. Lopes; M. E. Pereira; A. C. Duarte; R. W. Furness (Bulletin of Environmental Contamination and Toxicology, 2005)

A case of eumycetoma due to Madurella grisea in northern Brazil - Raquel Vilela; Olga M. V. Duarte; Carlos A. Rosa; Joao G. F. Castro; Sandra Lyon; Roberta L. Motta; Ana C. L. Moura (Mycopathologia, 2004)

Recruitment, mortality and growth of mangrove (Rhizophora sp.) seedlings in Ulugan Bay, Palawan, Philippines - C. Padilla; M.D. Fortes; C.M. Duarte; J. Terrados; L. Kamp-Nielsen (Trees, 2004)

Perturbations of malate accumulation and the endogenous rhythms of gas exchange in the Crassulacean acid metabolism plant Kalancho daigremontiana: testing the tonoplast-as-oscillator model - TomaszP. Wyka; Andreas Bohn; HeitorM. Duarte; Friedemann Kaiser; UlrichE. Lttge (Planta, 2004)

Aflatoxin Binders II: Reduction of aflatoxin M1 in milk by sequestering agents of cows consuming aflatoxin in feed - Duarte E. Diaz; Winston M. Hagler; John T. Blackwelder; Julie A. Eve; Brinton A. Hopkins; Kevin L. Anderson; Frank T. Jones; Lon W. Whitlow (Mycopathologia, 2004)

The Response of Experimental Rocky Shore Communities to Nutrient Additions - Tor L. Bokn; Carlos M. Duarte; Morten F. Pedersen; Nuria Marba; Frithjof E. Moy; Cristina Barrn; Birger Bjerkeng; Jens Borum; Hartvig Christie; Silke Engelbert; Frank L. Fotel; Espen E. Hoell; et al. (Ecosystems, 2003)

Hypersensitivity of Fagus sylvatica L. against leaf galling insects - G. Wilson Fernandes; Heitor Duarte; Ulrich Lttge (Trees, 2003)

Cerebral Toxoplasmosis After Autologous Peripheral Blood Stem Cell Transplantation - M. Lpez-Duarte; A. Insunza; E. Conde; A. Iriondo; F. Mazorra; A. Zubizarreta (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Movement sway: changes in postural sway during voluntary shifts of the center of pressure - Mark L. Latash; Sandra S. Ferreira; Silvana A. Wieczorek; Marcos Duarte (Experimental Brain Research, 2003)

Effects of Zinc upon Tolerance and Heavy Metal Uptake in Alfalfa Plants ( Medicago sativa ) - J. R. Peralta-Videa; J. L. Gardea-Torresdey; J. Walton; W. P. Mackay; M. Duarte-Gardea (Bulletin of Environmental Contamination and Toxicology, 2003)

Effects of melatonin on orofacial movements in rats - Abílio V.; Vera J.; Ferreira L.; Duarte C.; Carvalho R.; Grassl C.; Martins C.; Torres-Leite D.; Bignotto M.; Tufik S.; de Ribeiro; Frussa-Filho R. (Psychopharmacology, 2002)

Phylogenetic analysis of five Portuguese strains of FIV - A. Duarte; M. I. Marques; L. Tavares; M. Fevereiro (Archives of Virology, 2002)

Analysis of coastal lagoon metabolism as a basis for management - P. Duarte; J.M. Bernardo; A.M. Costa; F. Macedo; G. Calado; L. Cancela da Fonseca (Aquatic Ecology, 2002)

Pests and diseases in agroforestry systems of the humid tropics - G. Schroth; U. Krauss; L. Gasparotto; J. A. Duarte Aguilar; K. Vohland (Agroforestry Systems, 2000)

Plasmid transduction in Paenibacillus polymyxa - E.C.N. Ferreira; V.B. Clementino; G.F. Duarte; L. Seldin (World Journal of Microbiology and Biotechnology, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Putative association of a mutant ROM1 allele with retinitis pigmentosa - Amalia Martínez-Mir; Concha Vilela; Mònica Bayés; Diana Valverde; L. Dain; Magdalena Beneyto; Marina Marco; Montserrat Baiget; Daniel Grinberg; Susana Balcells; Roser Gonzàlez-Duarte; Lluïsa Vilageliu (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)